Floral volatile signatures as cultivar-specific metabolic fingerprints in mango (Mangifera indica L.) - Abeer Ali; Nimisha Sharma; Ansheef Ali; Haritha Bollinedi; Hatkari Vittal; Vishal Kumar; Akshay; Mukesh Shivran; Damini Singh; Jai Prakash; R.M. Sharma; A.K. Dubey (Biochemical Systematics and Ecology, 2026)

Changes in the spatial connection and synchronization of extreme rainfall events in recent decades over the Ganga and Yamuna River Basins of India - Ripunjay Pandey; Pragati Prajapati; Ashish Kumar Meena; Akshay Singhal; Sanjeev Kumar Jha; Kundan Kandhway (Atmospheric Research, 2026)

Photoacoustic Visualization of 7,12-Dimethylbenz[a]anthracene-Induced Breast Tumor by Multi-dosing of Tamoxifen-Loaded Albumin Nanoparticles - Akshay Kale; Vaishali; Nidhi Verma; Aseem Setia; Nandini Vinodrao Randhave; Komal Rani; Vikas Kumar; Madaswamy S. Muthu (Journal of Pharmaceutical Innovation, 2026)

Quality-by-Design Steered Development and Validation of Analytical Method for the Estimation of Etodolac: Integration of Monte Carlo Simulations and Green Analytical Principles - Akshay Kumar; Mohit Kumar; Pallavi Bassi; Balraj Saini; Narinderpal Kaur; Chander Parkash Dora; Gopal Thakur (Journal of Pharmaceutical Innovation, 2026)

Integrated bioprocess optimization of cellulase and xylanase production by Penicillium argillaceum using lignocellulosic agro-industrial residues - Sneha Akshay Ganpule; Utkarsha Manoj Lekhak (Brazilian Journal of Microbiology, 2026)

Application of chitosan-based nanomatrix enriched with Melaleuca alternifolia essential oil against the growth of storage fungi and aflatoxin B1 contamination in maize seeds - Vivekanand; Akshay Kumar; Vishal Gupta; Tanya Singh Raghuvanshi; Bhanu Prakash (Brazilian Journal of Microbiology, 2026)

Seasonal dynamics, size distribution profiles, and regional respiratory deposition risks of indoor and outdoor residential bioaerosols in Pune, India - Akshay Kale; P. Gursumeeran Satsangi (Aerobiologia, 2026)

Ultraviolet-C treatment of spices and herbs: A critical review on microbial safety and quality retention - Sandeep Sarkar; Akshay H. Dasalkar; Sudheer Kumar Yannam (Food Research International, 2026)

Evaluation of surface-functionalized multi-walled carbon nanotubes for tetracycline adsorption: Impact of matrix complexity and adsorbent reusability studies - Pragati Verma; Akshay Modi (Desalination, 2026)

Protective efficacy of a squalene adjuvanted oral inactivated vaccine against Streptococcus agalactiae in Nile tilapia - Jimsha EV; T.R. Akshay; Ritam Guha; Preetham Elumalai (Veterinary Immunology and Immunopathology, 2026)

Engineered bimetallic electrode materials for sustainable and selective electroreduction of CO2 into value-added products - Akshay Gandigawad; Hemavathi Manjunath; Chob Singh; Nitin K. Chaudhari; Hanimi Reddy Bapatu; Arvind H. Jadhav (Journal of Environmental Chemical Engineering, 2026)

Phenyl-bridged silica/polyacrylamide double-network aerogels with high compressive strength for efficient iodine vapor uptake and selective methylene blue adsorption - Qi Wang; Wonjun Lee; D.B. Mahadik; Akshay A. Ransing; Younghun Kim; Hyung-Ho Park (Journal of Environmental Chemical Engineering, 2026)

Influence of operating conditions on pyrolysis of oil palm mesocarp fibre biomass for sustainable biochar production and energy recovery - Heidi Teran-Pradilla; Akshay V. Bagde; Maria del Pilar Noriega E; Manosh C. Paul (Biomass and Bioenergy, 2026)

Epigenetic Regulation of Stress Tolerance and Fruit Quality in Fruit Crops - T. E. Tejas; Akshay Mehta; Satpal Baloda; Sarita Devi; Vikas Kumar Sharma; Aman Kumar (Applied Fruit Science, 2026)

In vitro evaluation of venom extracts of Sphecid wasps against phytopathogens of horticultural crops and mass spectrometric profiling of venom peptide components - C. Manasa; J. Jayappa; Jayashree Ugalat; Akshay Kumar; B. N. Maruthi Prasad; G. K. Ramegowda; T. B. Manjunatha Reddy; L. T. Nikita (International Journal of Tropical Insect Science, 2026)

Assessment of pathogenicity of indigenous entomopathogenic bacterial isolates against rice moth Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae) - Prasun Karmakar; Gurpreet Kaur Bhamra; Kajal Gupta; Akshay Mishra (Journal of Stored Products Research, 2026)

Divalent ion-crosslinked alginate–silica aerogels: A robust platform for efficient dye-contaminated wastewater treatment and thermal insulation - Akshay A. Ransing; Rushikesh P. Dhavale; Uzma K.H. Bangi; Jiseung Kim; Qi Wang; Shraddha B. Bhosale; HyunJee Heo; Vinayak G. Parale; Mukund G. Mali; Sandip Sabale; Hyung-Ho Park (Desalination, 2026)

Ionic network engineering for one-pot upcycling of waste acrylonitrile–butadiene–styrene - Siddhesh Sadashiv Rege; Ram Prasanth S.; Bhashkar Singh Bohra; Akshay Sunil Salvi; Ashok Misra; Suryasarathi Bose (Chemical Engineering Journal, 2026)

Correction: Circadian phenotype is associated with diurnal variation in human exercise performance - Akshay Singh; Sanjida Ahmed; Stuart J. Hesketh (European Journal of Applied Physiology, 2026)

Correction: Mechanistic insights into the toxicity of Strychnos nuxvomica L. seeds: Shodhana detoxification, 28-day repeated-dose toxicity and computational studies - Shamanand P. Mallapur; Banappa S. Unger; Mruthyunjay B. Patil; Akshay Shamnewadi; Vishal S. Patil; Veerkumar P. Japti (Toxicology and Environmental Health Sciences, 2026)

Toward non-transgenic hybrid microalgal platforms for astaxanthin production under CO2-rich conditions: A conceptual roadmap - Akshay Kumar; Reeta Rani Singhania; Vanshika Nimker; Yamini Sumathi; Cheng-Di Dong; Anil Kumar Patel (Algal Research, 2026)

Endophytic and rhizospheric plant growth-promoting bacterial diversity of Avicennia marina: implications for mangrove sustainability and resilience - Komal G. Antaliya; Manoj D. Godhaniya; Akshay H. Suthar; Nilam D. Vaghamshi; Smita B. Atara; Pravin R. Dudhagara; Rajesh K. Patel; Douglas J. H. Shyu (Biologia, 2026)

Optimization of plant growth regulators and media compositions to enhance in vitro gametic embryogenesis through anther culture of soybean [Glycine max (L.) Merr.] - Deepshikha Sharma; Ayyagari Ramlal; Pinkal Bishnoi; S. K. Lal; Dhandapani Raju; Manisha Saini; Akshay Talukdar; Bingi Pujari Mallikarjuna; Ambika Rajendran (Protoplasma, 2026)

Enhancing urban flood management for ungauged watersheds through adaptive mesh refinement and equation-based flow dynamics - Akshay Kumar; Nikhil Reddappa; Srinivas Rallapalli; Saumitra Rai; Rajiv Gupta (Hydrological Sciences Journal, 2026)

Risk of gastrointestinal bleeding with gabapentin versus duloxetine in older adults with neuropathic pain: a target trial emulation cohort study - Nirav Agrawal; Akshay Sharma; Aditya Chandrashekar; Muhammad Ali Ibrahim Kazi; Mitchell Karpman; Sanmeet Singh; Nargiz Muganlinskaya (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Comparative Plastome Analysis of Citrus sinesis with other Fruit Crops and cpSSR Development and Validation in Citrus Hybrids - Nimisha Sharma; Narendra Singh; Raushan Kumar; Mukesh Shivran; Akshay; Neha Sharma; Dhrumeshkumar Chavda; Lal Chand; A. K. Dubey; R. M. Sharma; S. K. Singh; Gyan Prakash Mishra; et al. (Tropical Plant Biology, 2026)

The rule of three: structural diversity, differential expression and distinct regulatory output of three MALT paralogues in salmonid fish - Akshay Patil; Annika Müller-Eigner; Henrike Rebl; Tom Goldammer; Alexander Rebl (Fish & Shellfish Immunology, 2026)

Global Water Scarcity: Understanding Challenges, Causes, and Mitigation Measures - Akshay Kumar Singh; Soham Mishra; Aman Kumar Singh; Mallikharjuna Prasad Polavarapu; Amit K. Singh; Sughosh Madhav; Ajai Singh; Manoj Kumar; Sushil Kumar Shukla (Water Conservation Science and Engineering, 2026)

Optimization of Ocimum sanctum-Mediated Tranilast-Loaded Silver Nanoparticles in a Thermosensitive PDLLA-PEG-PDLLA Hydrogel: Green Synthesis, Characterization, and Cytotoxic Efficacy Against Triple-Negative Breast Cancer Cells - Shraddha Ram; Anil T. Pawar; Amol A. Tagalpallewar; Akshay M. Baheti (Journal of Pharmaceutical Innovation, 2026)

Biophytum sensitivum: a promising herbal diet supplement for enhancing growth, immune response, antioxidant status, and disease resistance in Nile tilapia (Oreochromis niloticus) - Akshay Thuruthiyil Rajesh; Preetham Elumalai (Fish Physiology and Biochemistry, 2026)

The Vascular Genome as a Therapeutic Target: A Systematic Review of CRISPR-based Gene Editing In Vascular Disease - Abiya Ahad; Darshan Hullon; Tanya Singh; Sultan Mujib Dabiry; Lalenthika Sakthivel; Jeel Padaria; Akshay Singh Rekhraj; Aditya Bhattacharjee (Cardiovascular Toxicology, 2026)

Comprehensive study on phytochemical constituents and bioactive potential of aerial part extracts of Strobilanthes attenuata: an underexplored medicinal plant - Anantpreet Kaur; Akshay Kumar; Harpreet Walia; Samriti Khosla (Plant Biosystems, 2026)

Whole genome analysis reveals chromosomal and plasmid-mediated convergence of drug resistance in Klebsiella pneumoniae isolates - Dhinakaran Irusan; Akshay Sadanand Dangari; Varsha Prakash Shetty; Iddya Karunasagar; Vijaya Kumar Deekshit; Anusha Karunasagar (Antonie van Leeuwenhoek, 2026)

Association studies of stem characteristics and cell wall polymers for genetic enhancement of lodging resistance in rice - Kavya Zoopally; Jyothi Badri; Radhika Kommineni; Sanjeeva Rao Durbha; Akshay Mamidi; Kamala Devi Datla; Padmashree Revadi; Harshavardhan Rayudu Jamedar; S. V. Sai Prasad; Raman Meenakshi Sundaram (Journal of Plant Biochemistry and Biotechnology, 2026)

Indian homogeneous regional rainfall variability in recent decades - Akshay Kulkarni; P V S Raju; Archana Sagalgile; Bhupendra Bahadur Singh (Journal of Earth System Science, 2026)

Circadian phenotype is associated with diurnal variation in human exercise performance - Akshay Singh; Sanjida Ahmed; Stuart J. Hesketh (European Journal of Applied Physiology, 2026)
Purpose Time-of-day variation in exercise performance is well established, but the contribution of circadian phenotype to the magnitude of these differences remains unclear. This study examined diurnal variation in aerobic exercise performance and determined whether chronotype and sleep timing were associated with morning–evening differences in performance. Methods Twenty-four healthy young adults (12 male, 12 female) completed a randomised crossover protocol consisting of a 10-min cycling time trial performed in the morning (08:00–09:00) and evening (17:00–18:00). Pre-trial sleep, diet, and physical activity were standardised, and circadian phenotype was characterised using the Composite Morningness Questionnaire and 7-day actigraphy. Results Mean power, peak power, and distance covered were all significantly higher in the evening compared with morning ( p < 0.01). Chronotype ( r = − 0.47, p = 0.019) and sleep midpoint ( r = 0.52, p = 0.003) were significantly associated with the magnitude of the diurnal performance difference, accounting for 22% and 27% of the variance, respectively. Heart rate, blood lactate, and perceived exertion responses were similar between conditions, indicating comparable physiological strain. Core temperature was higher in the evening ( p = 0.026), but did not explain performance differences. Conclusions These findings demonstrate that endurance exercise performance is enhanced in the evening compared with the morning and suggest that behavioural markers of circadian phenotype are associated with the magnitude of diurnal variation in performance. Time-of-day and circadian phenotype should therefore be considered when optimising exercise testing and prescription.

A Review on Nanocarrier-Based Strategies for Sunitinib Delivery: Advances in Pharmacokinetic Enhancement and Targeted Theranostics - Mahesha Keerikkadu; Akshay Shetty; Raagul Seenivasan; Praveen Halagali; Vamshi Krishna Tippavajhala; Mahalaxmi Rathnanand (AAPS PharmSciTech, 2026)

COF-based hybrid composites as adsorbents and photocatalysts for antibiotics removal: Review - Akshay Verma; Gaurav Sharma; Sahil Rana; Yaksha Verma; Pooja Dhiman; Tongtong Wang (Journal of Water Process Engineering, 2026)

Monsoon-influenced Community of Parasitic Trematodes Within the First Intermediate Host (Pirenella Cingulata, Gastropoda) in Tropical Indian Mudflats - Ranjana Yadav; Pathan F.; Aniket Desai; Deepa Shashikant Yogi; Akshay Naik; Mandar Nanajkar (Estuaries and Coasts, 2026)

The Hydroclimate Paradox of the Indian Summer Monsoon Projections: Dual Amplification of Deficit and Excess Rainfall in CMIP6 Models - Akshay Kulkarni; P. V. S. Raju; Raghavendra Ashrit; Archana Sagalgile (International Journal of Climatology, 2026)
The Indian summer monsoon (ISM) governs the hydrological and agricultural foundation of South Asia, yet its response to anthropogenic warming remains uncertain and regionally diverse. Here we assess projected mean rainfall, variability and categorised monsoon extremes using six skill‐selected CMIP6 models (BCC‐CSM2‐MR, CMCC‐CM2‐SR5, FIO‐ESM‐2‐0, MCM‐UA‐1‐0, MIROC6, TaiESM1) evaluated against the high‐resolution IMD 0.25° dataset. Analyses are performed for the seasonal (JJAS) and monthly (June–September) scales under four Shared Socioeconomic Pathways (SSP1‐2.6, SSP2‐4.5, SSP3‐7.0, SSP5‐8.5). Century long observed records reveal a quasi‐stationary all‐India mean monsoon rainfall, accompanied by a marked increase in interannual variability consistent with progressive amplification of hydroclimatic extremes. The CMIP6 multi‐model ensemble (MME) reproduces this behaviour and projects a further 20%–35% rise in variability by the late 21st century. The coefficient of variation strengthens by 0.04–0.06 under high‐emission scenarios, with statistically significant regime shifts detected around 2040–2060. Enhanced seasonality is evident, with June and September exhibiting pronounced drying (≈−2 σ ) and July–August showing intensified wet excursions (≥ +3 σ ). Categorical analyses indicate a 40%–60% increase in moderate and extreme excess monsoon years and a 20%–30% rise in deficit years, while event intensities strengthen to +4 σ (wet) and –3 σ (dry). These concurrent amplifications of surplus and deficit rainfall define a hydroclimatic paradox: simultaneous amplification of mean rainfall and interannual variability, leading to heightened probabilities of both surplus and deficit extremes. The findings directly tangled with the reduced seasonal predictability and challenges for reservoir management and crop planning, as evidenced by projected increases in extreme excess years and intensified deficits. The warming climate is reorganising the ISM towards a high‐variance regime, challenging water security and adaptation planning across a region that depends critically on its seasonal rainfall predictability.

Colloidal Stability of Amorphous Nanoparticles in Solution: Impact of Stabilizer - Akshay Narula; Matthew J. Nethercott; Paroma Chakravarty; Na Li (Pharmaceutical Research, 2026)

Comparative 3E (energetic-exergetic-economic) assessment of pilot-scale single- and two-pass reverse osmosis systems for seawater desalination - Bhaumik Sutariya; Govind Amaliar; Akshay Kotangale; Bipinkumar Baladaniya; Gayatri Parmar; Puyam Sobhindro Singh (Journal of Environmental Chemical Engineering, 2026)

Polyacrylonitrile hollow fiber membranes for efficient CO2/N2 separation from flue gas: Fabrication and process optimization - Animesh Jana; Akshay Modi (Journal of Environmental Chemical Engineering, 2026)

Superhydrophobic electrospun nanofiber membranes for oil-water separation: A critical review on pioneering work, competitive material selection and future directions - Pradip P. Gaikwad; Rajaram S. Sutar; Sagar S. Ingole; Akshay R. Jundle; Rutuja A. Ekunde; Shanhu Liu; Sanjay S. Latthe (Journal of Environmental Chemical Engineering, 2026)

Boosting CO₂ electroreduction via in-situ fabricated CeO₂–MoO₃ heterostructures anchored on activated carbon cloth - Hemavathi Manjunath; Chob Singh; Akshay Gandigawad; Mohd Nor Faiz Norrrahim; Arvind H. Jadhav (Journal of Environmental Chemical Engineering, 2026)

Matrix-dependent modulation of chemical composition, volatile profile, and biological activity of kombucha beverages from different tea types - Akshay K. Chandran; Marcelina Stach; Jacek Łyczko; Zbigniew Lazar; Joanna Kawa-Rygielska; Helena Moreira; Anna Szyjka; Ewa Barg; Joanna Kolniak-Ostek (Food Chemistry, 2026)

Green nanomaterials from renewable Biomass: Sustainable Synthesis, environmental Applications, and Life-Cycle implications - Dilpreet Singh; Akshay Kumar; Pooja A. Chawla; Viney Chawla (Environmental Nanotechnology, Monitoring & Management, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

DDPM modelling of kinetic parameter sensitivity and bed size effects in biomass fluidised bed gasification - Md Nur Alam Mondal; Mohammed Al Rashdi; Akshay V. Bagde; Manosh C. Paul (Biomass and Bioenergy, 2026)

Enhancing biomass growth-dependent carbon dioxide sequestration potency of Azolla pinnata by optimizing temperature, light intensity and carbon dioxide concentration - Jatindra N. Bhakta; Akshay Sarkar; Pratap Majumder; Sukanta Rana; Bhabani Bhakta (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)

Hormone-optimized hypocotyl–epicotyl–cotyledonary tri-complex explant system enables efficient soybean transformation with reduced genotype dependence - J. Sushmitha; Durgeshwari Prabhakar Gadpayale; Navita Bansal; Ranjeet R. Kumar; G. Rama Prashat; Shivani Nagar; Soham Ray; Ashish Marathe; R. Dinesh Kumar; Akshay Talukdar; Giriraj Kumawat; Viswanathan Chinnusamy; et al. (Plant Cell Reports, 2026)

Rootstock-Mediated Nutrient Dynamics in Leaves, Buds and Panicles of Regular- and Alternate-Bearing Mango Cultivars - Hatkari Vittal; Nimisha Sharma; Akshay; R. M. Sharma; Nripendra Vikram Singh; Narendra Singh; Mahesh Chand Meena; Tirunagari Rupesh; Abeer Ali; Vishal Kumar; Anil Kumar Dubey; Gyan P. Mishra; et al. (Journal of Plant Growth Regulation, 2026)

AQbD enabled analytical method development and validation for simultaneous estimation of Asiaticoside (AC) and Chlorhexidine (CHX) in nanostructured lipid carriers - Akshay Kumar; Abhishek Chauhan; Devesh Kumar; Arpan Kumar Tripathi; Ankit Awasthi; Thakur Gurjeet Singh; Suresh Babu Kondaveeti; Mohit Kumar (Journal of Pharmaceutical Innovation, 2026)

Effect of dietary carrageenan supplementation on growth performance, digestive enzyme and antioxidant enzyme activity, immune gene expression, and capacity against S. agalactiae of Nile tilapia (Oreochromis niloticus) - Ishwarya Ramachandran; Akshay Thuruthiyil Rajesh; Preetham Elumalai (Fish Physiology and Biochemistry, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Mitochondrial Dysfunction Predisposes Radioresistant Insect Cells to Ionizing Radiation by Impairing DNA Repair - Shubhankar Suman; Akshay Pandey; Rakesh Kumar Seth; Sudhir chandna (Cell Biochemistry and Biophysics, 2026)

Dynamics of the Arabian Sea Low-Level Jet and its influence on Indian monsoon extremes - Archana Sagalgile; P. V. S. Raju; Akshay Kulkarni (Acta Geophysica, 2026)

Modeling spinal cord injury: bridging in vitro systems and in vivo complexity - Rutuja Satvase; Saumya Jaiswal; Manjeet Chopra; Hemant Kumar; Akshay Srivastava (In vitro models, 2026)

Corrigendum to “Current status of mangrove conservation efforts in Qatar: A review”[Reg. Stud. Mar. Sci., vol. 79 (2024) 103822] - Pavithra S. Pitumpe Arachchige; Marcela Rondon; Abhilash Dutta Roy; Michael S. Watt; Mollie Davies; Dhouha Ouerfelli; Ewane Basil Ewane; Ammar Abulibdeh; Meshal Abdullah; Talal Al-Awadhi; Akshay Sharma; Ricardo Martínez Prentice; et al. (Regional Studies in Marine Science, 2026)

Effect of conventional processing conditions on the occurrence of 5-hydroxymethylfurfural (HMF) and furfural in a selected edible insect species (Acheta domesticus (L.)) - Marios Psarianos; Hülya Altuntaş; Akshay D. Sonawane; Oliver K. Schlüter (Food Control, 2026)

Computational examination of magainin-I-KL mediated disruption of E. coli biofilms via CsgA amyloid interference - A. S. Vinutha; S. Akshay; S. G. Sree Agash; G. Chandrasekhar; Asmita Bhattacharya; R. Rajasekaran (Archives of Microbiology, 2026)

Enhanced production of enzyme cocktail by Bacillus cereus MCCB 101 using response surface methodology for aquafeed supplementation - Limmy Thazhunga Pailykutty; Akshay Puthumanakudy Sajeev; Riya George; Gopika Venu Sreebindu; Valsamma Joseph; Issac Sarojini Bright Singh (Biologia, 2026)

Thermo-Sensitive Polymeric Networks for Next-Generation Wound Management: A Review - Akshay Kumar; Prachee Nirmale; Suresh Babu Kondaveeti; Arpan Kumar Tripathi; Jailani Shiekmydeen; Sagar Nanaso Salunkhe; Gurjeet Singh Thakur; Mohit Kumar (AAPS PharmSciTech, 2026)

Application of bioaugmentors as Immobilized Microbial Consortia (IMC) for sustainable seed production of Etroplus suratensis in semi-intensive brackish-water earthen ponds under an Ecosystem-based Approach to Aquaculture (EAA): A pilot-scale field validation - Suresh Kunjiraman; Akshay P.S; Keerthana P.V; Riya George; Ammu Thomas; Lakshmi Gopakumar; Manomi Sarasan; I. S. Bright Singh; Jayesh Puthumana (Aquaculture International, 2026)

Environmental implications of coal mining and its sustainable mitigation by Phytoremediation: A comprehensive review - Akshay Kumar Singh; Jatin Kumar Choudhary; Mallikharjuna Prasad Polavarapu; Sushil Kumar Shukla; Ajai Singh; Manoj Kumar (Environmental Monitoring and Assessment, 2026)

Retraction notice to “Levothyroxine synthesis impurities are neither mutagenic nor genotoxic: Insilico, Ames test and micronucleus test studies” [Mutat. Res. - Genet. Toxicol. Environ. Mutagenesis 898 (2024) 503796] - Rajesh Rane; Akshay Prabhune; Dileep Kumar; Ajay Kumar; Madhur Sewlikar; Mugdha Suryawanshi; Bharat Satpute; Bapu Gawade; Sachin Sakat (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

First report of fatal feline pulmonary tuberculosis caused by the emerging zoonotic pathogen Mycobacterium orygis in a cat from India - Namita Mitra; Abhilash Jadhao; Akanksha V. Dhende; Akshay P. Hendre; Sabhanpreet Singh; Aishwarya Ramesh; Akaram T. Bagal; Hitesh N. Pawar (Veterinary Research Communications, 2026)

Feedbacks in a mixed mycorrhizal rainforest in Sri Lanka are more stabilizing in the field than in the shadehouse - Akshay Surendra; H. K. Mahesha Lakmali; H. A. Shashikala Madhubhani; H. M. S. Chaturanga Jayathilaka; K. M. Upul Shantha; Mark S. Ashton; Sisira Ediriweera; Liza S. Comita (Plant and Soil, 2026)

Rapid strengthening of tropical cyclones and their characteristics across the decades over the North Indian ocean - Akshay Kumar Sagar; Priyankar Kumar; Akshat Dimri (Ocean Dynamics, 2026)

Groundwater Potential Zones and Resource Estimation: A Case Study in Wainganga Basin, Central India Using AHP and Geospatial Techniques - Akshay R. Kharve; Nepal C. Mondal; Iswar C. Das; Venkatarao Ajaykumar (Journal of the Indian Society of Remote Sensing, 2026)

Guideline-directed heart failure pharmacotherapy and depression/anxiety: a scoping review of heart failure and related cardiovascular populations - Darshan Hullon; Danya Ansari; Abiya Ahad; Dyana Nasif; Ahmad Mustafa; Hamza Sohail Ansari; Akshay Singh Rekhraj (European Journal of Clinical Pharmacology, 2026)

Eco-friendly Suppression of Xanthomonas axonopodis pv. punicae: the Role of Lactobacillus helveticus PMP-6 in Pomegranate Disease Management - Pravin Vasantrao Deshmukh; Prakash Ramrao Thorat; Sopan Ganpatrao Wagh; Akshay Milind Patil; Vrunal Vishwasrao More; Rohini Ravindra Shivshran (Current Microbiology, 2026)

Advances in Nanoparticle-Based Vitamin Delivery Systems for Precision Nutrition and Improved Bioavailability - Sathvik Chennamsetty; Mahesha Keerikkadu; Akshay Shetty; Mahalaxmi Rathnanand (AAPS PharmSciTech, 2026)

Microneedle-Assisted Delivery of Biologics: From Large Molecules to Cancer Vaccines - Salma Younas; Mohit Kumar; Ramsha Khalid; Kirthana Gopal; Akshay Kumar; Pornanong Aramwit; Syed Mahmood (AAPS PharmSciTech, 2026)

Degradation of water contaminants by barium titanate (BaTiO3)-based materials: A critical review - Sahil Rana; Akshay Verma; Pooja Dhiman; Ackmez Mudhoo; Gaurav Sharma (Journal of Water Process Engineering, 2026)

In-situ fabrication of magnetic nanoparticle-decorated rGO/TiO2@MXene aerogels for enhanced visible-light-driven degradation of organic pollutants - Rushikesh P. Dhavale; Varsha D. Phadtare; Sagar A. Chaudhari; Mukund G. Mali; Vinayak G. Parale; Santosh V. Mohite; Donghwa Lee; Haryeong Choi; Akshay A. Ransing; Jiseung Kim; Sun Hee Kim; Prashant B. Patil; et al. (Journal of Water Process Engineering, 2026)

Fabrication and characterization of corn-silk biochar@Fe3O4 composite for the adsorption of malachite green dye - Akshay Verma; Pooja Dhiman; Chin Wei Lai; Alberto García-Peñas; Gaurav Sharma (Waste Disposal & Sustainable Energy, 2026)
The unregulated discharge of toxic dyes and agrochemicals resulting from industrial processes poses serious risks to aquatic and terrestrial ecosystems, highlighting the need for efficient remediation processes. In this work, a new corn silk-derived biochar/iron oxide (Fe 3 O 4 ) composite (BCCS@Fe 3 O 4 ) was synthesised via an in situ co-precipitation technique to effectively remove malachite green (MG) dye from aqueous solutions. The uniqueness of this study stems from the innovative use of corn silk, an agricultural waste, as a sustainable biochar precursor combined with Fe 3 O 4 nanoparticles to achieve both high adsorption capacity and magnetic recoverability. The prepared composite exhibited a high surface area, well-developed porosity, and strong magnetic properties that enabled efficient separation and reuse. Remarkably, the BCCS@Fe 3 O 4 composite exhibited superior adsorption uptake of 1000 mg/g, substantially surpassing conventional biochar and many previously reported adsorbents. The improved performance was due to electrostatic attraction, hydrogen bonding, and π–π interaction between dye molecules and the composite surface. The adsorption behaviour was well described by the Langmuir isotherm model, suggesting a monolayer adsorption pattern. Furthermore, the kinetic studies align with the pseudo-second-order model, indicating that chemisorption was the dominant mechanism governing the adsorption process. In addition, the material exhibited high recyclability, retaining 88.39% adsorption over four cycles. These findings highlight the promise of BCCS@Fe 3 O 4 composite as a low-cost, eco-friendly, and recyclable adsorbent for wastewater treatment processes. Graphical abstract

Statistical disaggregation approach for generating hourly precipitation in mountainous regions preserving complex temporal patterns - Nibedita Samal; K. V. Meenakshi; Akshay Singhal; Sanjeev K. Jha; Fabio Oriani (Stochastic Environmental Research and Risk Assessment, 2026)

Visnagin attenuates thioacetamide-induced kidney damage through suppression of renal injury marker, oxidative stress, inflammation, apoptosis, and TGF-β-mediated renal fibrosis - Akshay Amruta Navghare; Sonu Rajput; Poonam Yadav; Sumeet Kumar Singh; Yogender Goswami; Jasvinder Singh Bhatti; Umashanker Navik (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Anatomy of moist heatwaves in India during the summer monsoon season - Akshay Deoras; Andrew G. Turner; S. Lekshmi; Cathryn E. Birch; Ambrogio Volonté; Arathy Menon; Reinhard K. H. Schiemann; Laura J. Wilcox (Climate Dynamics, 2026)
Moist heat impairs the human body’s ability to cool through sweat-based evaporative cooling, posing a serious health risk. In India, this risk is especially acute, since the Indian summer monsoon (ISM) brings abundant moisture, and socio–economic conditions significantly increase the exposure and vulnerability to moist heat. However, there is a limited understanding of the characteristics and large-scale drivers of moist heatwaves during the ISM. This study uses the ERA5 reanalysis to analyse moist heatwaves and their relationship with active and break periods of the ISM during 1940–2023. An empirical orthogonal function analysis of daily maximum wet-bulb temperature (T w ) anomalies reveals that the first two principal components (PCs) explain key patterns of variability of moist heatwaves, with PC1 controlling their occurrence and PC2 controlling their spatial extent. Whilst breaks in the monsoon favour moist heatwaves in eastern and peninsular India, active rainfall events, corresponding to phases 5–7 of the Boreal Summer Intraseasonal Oscillation, favour moist heatwaves in northern and northwestern India. Specific humidity plays a larger role than dry-bulb temperature in controlling T w variability in India. The results of this study reveal important characteristics of moist heatwaves during the ISM and offer potential for developing forecasting tools, which could ultimately benefit stakeholders in India.

Activated Platelet-Rich Plasma Fibrin Scaffolds Enhance Axonal Regeneration and Functional Recovery Following Spinal Cord Injury - Leena R. Chaudhari; Akshay A. Kawale; Omkar Sonkawade; Mrunal Damle; Jitendra Patil; Sangeeta Desai; Meghnad G. Joshi (Annals of Biomedical Engineering, 2026)

Quantitative assessment of urban flood vulnerability using the Livelihood Vulnerability Index approach in the westernmost coastal metropolis of Mumbai, India - Rohit Mann; Neha Khajuria; Deepak Saini; Anju Gupta; Amit Dhorde; Akshay Yadav; Somvir Gill (Environmental Science and Pollution Research, 2026)

Re-imagining T-cell receptor signaling: parallel paths may be key to discriminatory power - Akshay Tiwari; Narendra M Dixit (Journal of Biosciences, 2026)

Spatial variability and multivariate assessment of soil properties and nutrient availability in mango-supporting soils of the Western Ghats, India - Akshay Chavan; Manoj Wahane; Nitin Khobragade; Vijay Damodhar; Suresh Dodake; Jagdish Prasad; Indal Ramteke (Environmental Monitoring and Assessment, 2026)

Visible light activated TiO₂/Nanolayered α-MoO₃ Heterostructure for photocatalytic dye degradation and forensic fingerprint imaging - Lasubon Syrti; Akshay Arjun; Priyanka K.P. (Journal of Water Process Engineering, 2026)

Predation risk magnifies fungicide-driven suppression of keystone shredder feeding and behaviour, slowing freshwater leaf-litter degradation - Akshay Mohan; Blake Matthews; Katja Räsänen (Environmental Pollution, 2026)

Taming the non-linearity: An iterative conceptual routing model for improving flood peak prediction - Ekant Sarkar; Akshay Kadu; S.L. Kesav Unnithan; Basudev Biswal (Environmental Modelling & Software, 2026)

Portal for high-precision atomic data and computation - Amani Kiruga; Charles Cheung; Dmytro Filin; Parinaz Barakhshan; Akshay Bhosale; Vipul Badhan; Bindiya Arora; Rudolf Eigenmann; Marianna S. Safronova (Computer Physics Communications, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Upcycling of waste Geranium leaves into biochar for soil amendment - Chalasani Danteswari; Pullabhotla V.S.R.N. Sarma; Akshay Rao; Dharani Kumar Chennamsetty; Ravikiran Nowduru; Appa Rao Podile; Venkata Satya Siva Srikanth Vadali (Biomass and Bioenergy, 2026)

Assessment of the atmospheric drivers of flash drought in India through complex causal pathways - Akshay Bajirao Pachore; Renji Remesan; Jayanarayanan Kuttippurath (Theoretical and Applied Climatology, 2026)

Optimizing GEDI Footprint Selection for Forest Canopy Height Estimation in the Western Himalaya Using Multi-sensor Data - Akshay Paygude; Hina Pande; Poonam Seth Tiwari; Praveen Kumar Varma; Manoj Kumar (Journal of the Indian Society of Remote Sensing, 2026)

Anti-osteoarthritic effects of stem bark extract of Anogeissus latifolia: a comprehensive in-vivo study - Chaitanya B. Sirsath Patil; Shreyas R. Shinde; Riddhi S. Deka; Akshay M. Baheti; Shuchi Nagar; Shvetank Bhatt; Anil T. Pawar (Inflammopharmacology, 2026)

Residential indoor and outdoor exposure to VOCs and NO2: insights from a multi-city pilot study in India - Prince Vijay; Akshay Kumar; Shreya Dubey; Rajdeep Singh; Vinayak Sahota; Sonali Borse; Harish C. Phuleria (Environmental Geochemistry and Health, 2026)

Investigating the signature of thunderstorm-generated gravity waves on low-latitude ionospheric dynamics - Akshay S. Patil; Rani P. Pawar; Aditi D. Yadav; Dada P. Nade; T. Dharmaraj; Sanjay V. Pore; Sambhaji M. Pawar; Sunil D. Pawar (Advances in Space Research, 2026)

Unified Phenological Characterization of Fruit Crops Using the Extended BBCH Scale - Aman Kumar; Akshay Mehta; Vikas Kumar Sharma; Sushil Sharma; Pravin Kumar Sharma; Prince (Applied Fruit Science, 2026)

Synergistic Potential of Microbial Consortia for the Management of Fusarium Wilt and Growth Enhancement in Strawberry (Fragaria ananassa) - Manica Tomar; Akshay Rana; Debjeet Sharma; Gopal Singh; Anjali Chauhan (Applied Fruit Science, 2026)

In silico screening of IMPPAT-derived phytochemicals targeting ERG6 and drug resistance–associated proteins in drug-resistant Candida albicans: virtual screening and molecular dynamics using alphafold models - Akshay Kisan Mundhe; Premanand Adaikalasamy; Reena Rajkumari Baskaran (In Silico Pharmacology, 2026)

Smart Stings of Nature: Harnessing Microneedles Assisted Targeted Phytoconstituent Delivery for Dermatological Disorders - Akshay Kumar; Suresh Babu Kondaveeti; Arpan Kumar Tripathi; Mohit Agrawal; Thakur Gurjeet Singh; Devesh Kumar; Mohit Kumar (AAPS PharmSciTech, 2026)

Matairesinol regulates TGF-β-induced EMT and TGF-β associated crosstalk with Wnt Signaling in PC3 prostate cancer cells: An omics-guided therapeutic insight - Rama Rajadnya; Prajakta Patil; Akshay Deotare; Aniket Mali (Toxicology and Applied Pharmacology, 2026)

Navigating rice culm resilience: High-throughput quantitative trait locus mapping in indica and tropical japonica derived population - Akshay Mamidi; Lavuri Krishna; Jyothi Badri; Kalyani M. Barbadikar; Sanjeeva Rao Durbha; SV Sai Prasad; Raman Meenakshi Sundaram (Plant Science, 2026)

Ionospheric response to lightning activity during cyclone Tauktae over the Arabian Sea - Akshay S. Patil; Aditi D. Yadav; Bhushan Vibhute; Dada P. Nade; T. Dharmaraj; Sambhaji M. Pawar; Sunil D. Pawar (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Signaling Pathways Triggering Therapeutical Potential of Marine-Derived Polysaccharides in Alzheimer’s Disease: A Recent Review - Devesh Kumar; Suresh Babu Kondaveeti; Mohit Agrawal; Akshay Kumar; Ankit Awasthi; Syed Mahmood; Thakur Gurjeet Singh; Mohit Kumar (Molecular Neurobiology, 2026)

Factors determining the occurrence and spatial association of meso-carnivores in the semi-arid landscape of Madhya Pradesh, India - Shantanu Sharma; Debashish Panda; Akshay Jain; Rajasekar Rajaraman; Kamlesh K. Maurya; Randeep Singh (Mammal Research, 2026)

Regulation and Therapeutic Intervention of Bacterial Biofilms - Nicole Irizarry-Tardi; Jathya C. Karunathilaka; Nicholas L.F. Gallina; Akshay Krishnakumar; Weicang Wang; Rahim Rahimi; Arun K. Bhunia (Current Clinical Microbiology Reports, 2025)
Purpose of Review Bacteria are highly adaptive organisms that have evolved various survival strategies to persist and thrive in hostile environments. They especially form polymicrobial biofilms with an intricate microbial community network in a highly regulated fashion. This review covers recent findings on bacterial biofilm pathogenesis and innovative multidisciplinary therapeutic interventions for clinical infections. Recent Findings Bacterial cyclic dimeric guanosine monophosphate (cyclic di-GMP) is a central regulator for biofilm pathogenesis orchestrated by quorum sensing (QS) molecules, allowing prolonged survival, host immune evasion, antibiotic resistance, and augmented virulence with severe health consequences. Biofilms associated with medical devices or wounds pose significant risks due to sessile bacteria, which are notably more resistant to eradication than their planktonic counterparts due to diminished metabolic activities. This phenomenon complicates the treatment of biofilm-associated infections and exacerbates the persistence of chronic illnesses. Novel intervention strategies include CRISPR/Cas9, QS inhibitors, natural antimicrobial peptides, probiotics, antimicrobial nanomaterials, and advanced biophysical remedies. Summary A deeper understanding of the regulation of biofilm pathogenesis will facilitate the development of novel interventions suitable for clinical biofilms in various chronic infections.

Challenges and future perspectives in postharvest cold storage: technological review on sustainable and efficient cold storage of fresh produce - Tuany Gabriela Hoffmann; Carolina Krebs de Souza; Akshay D. Sonawane; Ulrike Praeger; Felix Büchele; Daniel Alexandre Neuwald; Reiner Jedermann; Manfred Linke; Barbara Sturm; Pramod V. Mahajan (Food Research International, 2025)

Demystifying the potential pharmaceutical attributes of corn silk: An agriculture bio-waste - Sachin S. Mali; Dipak S. Thorat; Sudarshan Singh; Yogesh V. Ushir; Prajakta R. Patil; Dhanashree R. Davare; Pooja V. Nagime; Snehal S. Patil; Akshay Kundale (Food and Humanity, 2025)

Extracellular vesicle proteomic expression is influenced by mining tenure in former uranium miners - Mijung Oh; Eunju Lim; Onamma Edeh; Sydnee Yazzie; Deborah Kanda; Li Luo; Quiteria Jacquez; Ting Jiang; Prajakta Adsul; Jason Weick; Akshay Sood; Katherine E. Zychowski (Environmental Research, 2025)

Strong yet mechanically flexible thick necked aerogels fabricated via in situ-catalyzed epoxy-thiol polymerization with necking enhancement: A finite element simulation and wastewater treatment applications - Vinayak G. Parale; Haryeong Choi; Varsha D. Phadtare; Rushikesh P. Dhavale; Younghun Kim; Akshay A. Ransing; Ivan I. Smalyukh; Michele Meo; Hyung-Ho Park (Chemical Engineering Journal, 2025)

Signalling pathways triggering therapeutic marine algae-derived natural polysaccharides for effective wound healing: A recent review - Suresh Babu Kondaveeti; Arpan Kumar Tripathi; Devesh Kumar; Akshay Kumar; Thakur Gurjeet Singh; Syed Mahmood; Kajal Ghosal; Ankit Awasthi; Mohit Kumar (Carbohydrate Polymers, 2025)

Hydrodynamics of in-canopy flow in synthetically generated coral reefs under oscillatory wave motion - Akshay Patil; Clara García-Sánchez (Coastal Engineering, 2025)

Retrieval of satellite-derived black carbon concentration and mitigation approaches for Karnataka, India - Narayan Kayet; Likitha M P; Akshay Kumar V G; Geeta Hegde; Tejaswini Eregowda; Chandana M C (Atmospheric Environment, 2025)

Assessment of heavy metal contamination in roadside soil and its uptake by selected tree species in urban and semi-urban regions - Akshay Kumar Singh; Jatin Kumar Choudhary; Sushil Kumar Shukla (Urban Ecosystems, 2025)

In Silico Discovery of Tanshinone I, a Diterpenoid from Salvia miltiorrhiza (Danshen), as a Dual Antiviral Natural Inhibitor Targeting Conserved Allosteric Sites of HMPV and HRSV RNA-Dependent RNA Polymerases - Sayantika Debnath; Uddalak Das; Akshay Uttarkar; Vidya Niranjan; Arkajit De (Journal of Pharmaceutical Innovation, 2025)

Cyclic Behavior of Unsaturated Sandy Soil: Effects of Compaction, Saturation, and Suction under Traffic-Like Loading - Bhargavi Chowdepalli; Akshay Singh Rathore; Kenji Watanabe (Geotechnical and Geological Engineering, 2025)

Heavy metal-induced neurotoxicity and endocrine disruption from e-waste: emerging health challenges and intervention strategies - Debika Sarmah; Akshay Nirala; Hemanga Hazarika (Toxicology and Environmental Health Sciences, 2025)

Forest dependence and livelihood dynamics: A study of non-timber forest products based economies in forest fringe communities of a dry deciduous forest region of West Bengal - Bipul Paul; Trishita Debnath; Akshay Rana; Nilanjana Das Chatterjee (Agroforestry Systems, 2025)

Variability of Fine Particulate Matter (PM1.0 and PM2.5) and its Oxidative Potential at Different Locations in the Northern Part of India - Tulika Tripathi; Akshay Kale; Madhu Anand; P. G. Satsangi; Ajay Taneja (Aerosol Science and Engineering, 2025)

Facile One-Step Synthesis of Carbon Quantum Dots Via Hot Injection for High-Efficiency Dye Photodegradation - Naina Lohia; Akshay M. Achari; G. Swati; Shailesh Narain Sharma (Journal of Fluorescence, 2025)

Psychobiotics and the gut-brain axis: advances in metabolite quantification and their implications for mental health - Vincent Owusu Kyei-Baffour; Akshay Kumar Vijaya; Aurelijus Burokas; Eric Banan-Mwine Daliri (Critical Reviews in Food Science and Nutrition, 2025)

Unravelling resistance to sunflower necrosis disease: a molecular diagnostic and physiological trait-based approach to identify TSV-resilient germplasm - Chaitra Govinakovi Veereshappa; Parameswari Balasubramaniam; Pranusha Pulivendula; Sakhare Akshay Sureshrao; Anitha Kodaru; Bhaskar Bajaru; Lakshman Saravanan; Celia Chalam Vasimella; Gyanendra Pratap Singh (Journal of Plant Pathology, 2025)

First report of Alternaria tenuissima causing leaf blight disease on Madhuca longifolia (Mahua) seedlings in India - K. Darshan; Charishma Krishnappa; Fatima Shirin; S.N. Mishra; Sourabh Dubey; Dolly Parte; H.M. Akshay Kumar (Physiological and Molecular Plant Pathology, 2025)

Application of hybrid gradient boosting machine to reliably predict rate of penetration - JiaNing Zhang; Farag M.A. Altalbawy; Tarak Vora; R. Manjunatha; Debasish Shit; Nargiza Kamolova; Akshay Kumar; Atreyi Pramanik; Ajay Sharma; Tamam Ali Abd Ulabbas Abedi; Ahmad Abumalek; Mohammad Mahtab Alam; et al. (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Partition–diffusion–reaction bounds for thin-film membrane formation kinetics - Akshay Deshmukh; Menachem Elimelech; John H. Lienhard (Chemical Engineering Journal, 2025)

Impact of primary aerosol particles on size specific oxidative potential and its relationship with air quality and hazard index - Atar Singh Pipal; Sachin D. Ghude; P.G. Satsangi; Milindkumar Yashvant Bhatkar; Akshay Kale; Sandip S. Nivdange; M. Nageswar Rao; Arkabanee Mukherjee; Akash S. Vispute; Hardeep Sharma; Vikash Kumar; Prasanna Lonkar; et al. (Atmospheric Environment, 2025)

Network pharmacology, molecular docking, molecular dynamics, and ADMET analysis of Curcuma caesia phytoconstituents against rheumatoid arthritis - Akshay Shamnewadi; Banappa S. Unger; Partha Palit; Sunil S. Jalalpure; Omkar Mali; Vishal S. Patil; Jagadeesh Dodakallanavar; Harish R. Darasaguppe; Shamanand P. Mallapur (In Silico Pharmacology, 2025)

Spectral Studies of Sm3+-doped Mg2GeO4 Nanophosphors: Realization of Orange-Red Emission for Solid-State Lighting Applications - Akshay Arjun; H. B. Premkumar; G. P. Darshan (Journal of Fluorescence, 2025)

Advances in Pharmaceutical Cocrystals and Nano-Cocrystals: Strategies for Enhancing Solubility and Translating to Clinical Use - Roshan P. Rao; Jawahar Natarajan; Samanwita Khanra; Jey Kumar Pachiyappan; Imrankhan Nizam; Akshay Muralidhara; Jubie Selvaraj; S. Selvamuthukumar (AAPS PharmSciTech, 2025)

Deep Neural Network-Based Risk Prediction of Glioblastoma Multiforme Recurrence - Disha Sushant Wankhede; Aniket K. Shahade; Priyanka V. Deshmukh; Akshay Manikjade; Makrand Shahade; Pritam H. Gohatre; Kanchan Tidke (Journal of Molecular Neuroscience, 2025)

Trade regulations drive improved global shark and ray management - Mark E. Bond; Hollie Booth; Akshay Tanna; Sarah L. Fowler; Carlos J. Polo-Silva; K.H. Stanley Shea; Floriane Cardiec; Elisabeth F. Mansur; Rima W. Jabado (Marine Policy, 2025)

Toward ecological forecasting of West Nile virus in Florida: Insights from two decades of sentinel chicken surveillance - J. Alex Baecher; V.A. Akshay; Robert P. Guralnick; Amy M. Bauer; Yasmin N. Tavares; Yesenia Sánchez; James T. Thorson; Lindsay P. Campbell (Science of The Total Environment, 2025)

A Bayesian reliability methodology for rock structures considering uncertainties in random field characteristics with limited data of rock properties - Akshay Kumar; Gaurav Tiwari (International Journal of Rock Mechanics and Mining Sciences, 2025)

Efficient induction of parthenogenetic haploids in African marigold (Tagetes erecta) L.) using Co60 gamma-irradiated pollen of French Marigold (Tagetes patula L.) - Eram Arzoo; Kavita Dubey; Rashmi Arora; Kanwar Pal Singh; Sapna Panwar; Akshay Talukdar; Bhupinder Singh; Mahesh Rao; Mariyam Firdous; Bharti Juneja; Reeta Bhatia (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Plants Response to Different Abiotic Stresses - Sami Jan; M. Ashraf Bhat; Akshay Kumar; M. Altaf Wani; Farooq Ahmad Bhat; Raihana H. Kanth; A. B. Shikari; Haleema Bano; Tabasum Manzoor; Heena Altaf; Noor-ul-Ain; Zafir Ahmad Naik (Journal of Crop Health, 2025)

Decoding Phytophthora meadii (McRae): the first genomic insights into the arecanut fruit rot pathogen - M. K. Rajesh; V. H. Prathibha; Bobby Paul; Roli Budhwar; Rohit Shukla; Akshay Dinesh; K. P. Gangaraj; R. Thava Prakasa Pandian; Jasmin Habeeb; B. J. Nirmal Kumar; M. Chaithra (Journal of Plant Pathology, 2025)

9-fluorenone-based synthetic sulfonamide compounds as dual inhibitors of SARS-CoV-2 Main-Protease and Papain-like Protease - Sudesna Das; Prasad Sunnapu; Mohammed Rafi; Yasmin Begum; Sudip Dey; Akshay Joshi; Nittu Singh; Krishan Gopal Thakur; Parasuraman Jaisankar; Umesh Prasad Singh (Molecular Diversity, 2025)

Quantifying the impact of urban geometric detail for urban air mobility risk forecasting - Akshay Patil; Clara García-Sánchez (Sustainable Cities and Society, 2025)

Black carbon emissions from road transport in Karnataka, India: High-resolution inventory and mitigation strategies - Narayan Kayet; Likitha M P; Geeta Hegde; Akshay Kumar V Ganeshker; Tejaswini Eregowda (Science of The Total Environment, 2025)

Assessing machine learning and Physics-Informed models for Multi-Lead time sea surface temperature prediction in the Arabian sea - Akshay Sunil; B. Deepthi; Muhammed Rashid; Rahul Sreedhar; Gaurav Ganjir; S. Adarsh (Stochastic Environmental Research and Risk Assessment, 2025)

Investigating Age-Specific Respiratory Deposition Doses of Traffic-Related Particles at Urban Intersections in Pune, India - Akshay Kale; P. G. Satsangi (Aerosol Science and Engineering, 2025)

Deployment of combining ability analysis to study gene action under different environments in okra [Abelmoschus esculentus (L.) Moench] - Arpita A. Patel; Rajesh D. Vekariya; Akshay I. Patel; K. G. Modha (Vegetos, 2025)

Analysis of urban flood vulnerability at the sub-city administrative unit level in Mumbai: A comparison over two time periods - Pragati Prajapati; Akshay Singhal; Sanjeev Kumar Jha (Urban Climate, 2025)

Removal of heavy metals from laboratory waste liquid (LWL) generated from water and wastewater analytical laboratories - Swati P. Dhenkula; Akshay D. Shende; Leena Deshpande; Girish R. Pophali (Process Safety and Environmental Protection, 2025)

Development and characterization of carrageenan-based antibacterial films incorporated with natural melanin pigment from niger seed hulls (Guizotia abyssinica) and their efficacy to enhance the shelf-life of strawberries - B.T. Sunil Kumar; Jeevan Prasad Reddy; V. Vanajakshi; Akshay H. Dasalkar; Sudheer Kumar Yannam; Umesh H. Hebbar; Sridevi Annapurna Singh (Food Control, 2025)

Micelle nanogel–based drug delivery system for lutein in ocular administration - Reeshma Shetty; Jobin Jose; Naseer Maliyakkal; Sandeep D. S.; Renjith P. Johnson; Akshay Bandiwadekar; Gopika Gopan; Sanjay R. Ugare; Namitha K. Preman (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Fish diversity and community structure during open and closed mouth states in Poovar—a small temporarily closed tropical Indian estuary - Sreekanth Giri Bhavan; Keerthana Prakash Sini; Akshay A. Kumar; Soorya Gopan; Arunima Biju Kumar; Shamini Mettincy Shaji; Kiranya Bella (Marine Biodiversity, 2025)

Integrating Quality by Design (QbD) in Phytosomal Drug Delivery: A New Era in Precision Phytotherapy - Sumant Kumar; Omar Awad Alsaidan; Sami I. Alzarea; Akshay Kumar; Suresh Babu Kondaveeti; Diksha Sharma; Mohit Kumar; Devesh Kumar (AAPS PharmSciTech, 2025)

Climate Response of the Seven Homogeneous Monsoon Rainfall Regions of India Using the SOLAR Geoengineering Simulation Datasets - Akshay Kumar Sagar; Arun Chakraborty (Aerosol Science and Engineering, 2025)

Synergistic effect of molybdenum and Rhizobium on growth and yield of vegetable cowpea (Vigna unguiculata (L.) Walp.) - Monu Kumari; Nitin B. Patel; Kapil Dev Ameta; Akshay Kumar Yogi; Harshit Kumar; Ayushi Jain (Vegetos, 2025)

Multiple object tracking with multi-view active vision to effectively find plant nodes in a cluttered tomato greenhouse - Xin Wang; Akshay K. Burusa; David Rapado-Rincón; Thomas A.W. Versmissen; Eldert J. van Henten; Gert Kootstra (Computers and Electronics in Agriculture, 2025)

Investigating apple surface condensation and mass loss with IoT and predictive modelling - Akshay D. Sonawane; Tuany G. Hoffmann; Reiner Jedermann; Manfred Linke; Pramod V. Mahajan (Postharvest Biology and Technology, 2025)

Waste to hydrogen: Steam gasification of municipal solid wastes with carbon capture for enhanced hydrogen production - Akshay V. Bagde; Manosh C. Paul (Biomass and Bioenergy, 2025)

Study of accumulated cyclone energy and associated drivers affecting tropical cyclone activities over the North Indian Ocean during the pre- and post monsoon season - Akshay Kumar Sagar; Arun Chakraborty; Swadhin Kumar Behera; Abhishek Kumar (Natural Hazards, 2025)

Grassland Bird Species Decline With Colonial‐Era Landscape Change in a Tropical Montane Ecosystem - Vijay Ramesh; Priyanka Hariharan; Pratik Rajan Gupte; Ashwini V. Mohan; V. A. Akshay; Amrutha Rajan; Chandrasekar Das; Ian Lockwood; V. V. Robin; Morgan W. Tingley; Ruth DeFries (Global Change Biology, 2025)
The impacts of colonial‐era ecosystem changes on tropical biodiversity are poorly understood. We analyzed a 170‐year dataset on land cover and bird observations in an Old World tropical montane landscape in the Western Ghats, India, to determine if and how historical landscape changes have impacted 85 bird species. A comparison of historical land cover and classified satellite imagery (1848–2018) revealed approximately an 80% decrease in grassland area and a concomitant increase in tea and timber plantations stemming from colonial‐era policies and associated legacies of large‐scale planting of cash crops and exotic woody species. We found that relative species abundances of about 90% of grassland birds have significantly declined while around 53% of forest bird species remained stable or even increased in relative abundance over the same period. Over 74% of generalist bird species have become more common over the same period, possibly due to reduced habitat specialization. Our findings show that colonial‐era policies, continued postindependence, of tree planting across open natural ecosystems have resulted in severe loss of grassland habitats and a concomitant decline in the relative abundance of grassland bird species.

Assessment of spatial variability in soil and leaf nutrients of mango orchards using geostatistical and multivariate approaches in the Himalayan foothills - Akshay Dhiman; Rakesh Sharma; Himanshu Mehta; Vaishali Sharma (Environmental Monitoring and Assessment, 2025)

SSL-NBV: A self-supervised-learning-based next-best-view algorithm for efficient 3D plant reconstruction by a robot - Jianchao Ci; Eldert J. van Henten; Xin Wang; Akshay K. Burusa; Gert Kootstra (Computers and Electronics in Agriculture, 2025)

ZIF-based hybrid magnetic nanocomposites for the removal of organic pollutants - Gaurav Sharma; Akshay Verma; Tongtong Wang; Amit Kumar; Pooja Dhiman; Genene Tessema Mola; Jinhu Zhi (Journal of Water Process Engineering, 2025)

Micro-macro–scale flood modeling in ungauged channels: Rain-on-grid approach for improving prediction accuracy with varied resolution datasets - Akshay Kumar; Sripali Biswas; Srinivas Rallapalli; Pratik Shashwat; Selva Balaji; Rajiv Gupta (Journal of Hydrology, 2025)

Chemical and toxicological characteristics of fine particles from festive fireworks in urban residential communities - Shreya Dubey; Vinayak Sahota; Akshay Kumar; Nidhi Prajapati; Vijaya Laxmi; Balram Dangi; Harish C. Phuleria (Atmospheric Environment, 2025)

Biomedical waste management: navigating the challenges to achieve the promise of sustainable development goal 3 - Varsha Prakash Shetty; Sadanand Dangari Akshay; Barani Devi Thilai; Vijaya Kumar Deekshit (Waste Disposal & Sustainable Energy, 2025)

Prediction of Air Quality Index (AQI) using machine learning-based tree models—a case study of Gurugram City, India - Akshay Kumar; Parveen Sihag; Karan Singh; Fatemeh Esmaeilbeiki; Balraj Singh; Hari Om (Theoretical and Applied Climatology, 2025)

Sodicity tolerance in Jamun (Syzygium cumini L. Skeels) genotypes based upon growth and physiological traits - Rajkumar; Ashwani Kumar; Anshuman Singh; Nirmal Singh; Akshay Kumar; Pratibha Poonia; Antim Kundu (Plant Physiology Reports, 2025)

Integrated omics analysis of rice gene expression profiles and microRNAs identifies crucial target genes for nitrogen use efficiency - Kalyani M. Barbadikar; Krishna Kant Talapanti; Sonali Bej; Suman Karre; Harish Kothandaraman; S. Malathi; Raghuveer Rao Puskur; Satendra Kumar Mangrauthia; Subrahmanyam Desiraju; S. R. Voleti; Akshay Sureshrao Sakhare; M. S. Anantha; et al. (Plant Physiology Reports, 2025)

Enhanced rainfall forecasting for Mumbai using data-driven ConvLSTM2D models at fine spatial and temporal scales - Akshay Sunil; Ajay Devda; R. Murthy; B. Deepthi (Natural Hazards, 2025)

Nanomaterial derived electroceuticals for personalized pain and inflammation: technologies and patents - Dilpreet Singh; Akshay Thakur; Kuldeep Singh (Nanotechnology for Environmental Engineering, 2025)

Evaluating Machine Learning Classifiers for IRS High Resolution Satellite Images Using Object-Based and Pixel-Based Classification Techniques - Akshay Kumar; Gaurav Kumar; Deshbhushan Savindra Patil; Rajiv Gupta (Journal of the Indian Society of Remote Sensing, 2025)

Heavy Metal Pollution in River Ulhas, Maharashtra, India: Unraveling Contamination Dynamics Through Pollution Indices, Multivariate Analysis, and Health Risk Assessment - Akshay Botle; Sayli Salgaonkar; Rahul Tiwari; Gayatri Barabde (International Journal of Environmental Research, 2025)

Enhancing virus resistance through pre-breeding and crossability experiments in okra (Abelmoschus esculentus (L.) Moench) - S. Santhiya; Ramesh Kumar Yadav; Suman Lata; Bhoopal Singh Tomar; Akshay Talukdar; Avinash Tomer; C. Vaishali; P. Prabhu; Koku Tara (Genetic Resources and Crop Evolution, 2025)

Mechanistic insights into the toxicity of Strychnos nuxvomica L. seeds: Shodhana detoxification, 28-day repeated-dose toxicity and computational studies - Shamanand P. Mallapur; Banappa S. Unger; Mruthyunjay B. Patil; Akshay Shamnewadi; Vishal S. Patil; Veerkumar P. Japti (Toxicology and Environmental Health Sciences, 2025)

A laboratory-scale recirculating aquaculture system for long-term experimental rearing of bivalves under minimal stress conditions for aquatic animal research - Soumya Balakrishnan; Ambadi Kannan Maliyekkal Sajeevan; Akshay P. S.; I. S. Bright Singh; Jayesh Puthumana (Aquaculture International, 2025)

Deep learning for automatic post-disaster debris identification for precise damage assessments using UAV footage - Gyan Prakash; Sindhuja Kasthala; Akshay Loya (Applied Geomatics, 2025)

Speciation in the Peninsular Indian Flying Lizard ( Draco dussumieri ) Follows Climatic Transition and Not Physical Barriers - Ramamoorthi Chaitanya; Aranya Dhibar; Akshay Khandekar; Channakesava Murthy; Shai Meiri; Praveen Karanth (Molecular Ecology, 2025)
Marked with high levels of endemism and in situ radiations, the Western Ghats mountains make for a compelling backdrop to examine processes that lead to the formation and maintenance of species. Regional geographic barriers and paleoclimatic fluctuations have been implicated as drivers of speciation, but their roles have not been explicitly tested in a phylogenomic framework. We integrated mitochondrial DNA, genome‐wide SNPs and climatic data to examine the influence of geographic barriers and climatic transitions in shaping phylogeography and potential speciation in the Peninsular Indian Flying lizard ( Draco dussumieri ). We found strong evidence for two independently evolving, geographically distinct, northern and southern lineages within D. dussumieri that diverged during the early Pleistocene, and a gradient of admixed populations across a broad hybrid zone in the Central Western Ghats. Migrations after initial divergence were continuous, but gene flow remained consistently below thresholds required to homogenise lineages. We found more support for isolation by environment (especially rainfall regimes) than by distance. The range‐break between lineages occurs at a transition zone in the Central Western Ghats that separates dissimilar rainfall regimes with no physical barriers. This limit is potentially an ecological barrier, which nevertheless was permeable during glacial maxima. We hypothesise that similar phylogeographic patterns will emerge in other widespread, wet‐adapted species in the Western Ghats that presumably endured the same climatic processes.

Establishment and molecular characterization of the novel cutaneous squamous cell carcinoma cell line from advanced-stage Indian patient - Darshan Mehta; Akshay Paradkar; Prakash Nayak; Bharat Rekhi; Bhabani Mohanty; Pradip Chaudhari; Sanjeev K Waghmare (Human Cell, 2025)
Cutaneous squamous cell carcinoma (CSCC) is the second most prevalent skin cancer with low metastatic potential; it poses significant morbidity challenges. CSCC possesses significant heterogeneity and the treatment presents a formidable challenge. To gain a clear insight into the diverse nature of these tumors, the development of an in vitro cell line model is essential. However, there are few cell lines that were established, and only one skin SCC cell line is available on the ATCC. In the present study, we established and characterized a novel ACSCC1 cell line from the advanced-stage treatment naïve cutaneous SCC originating from the forearm of the Indian patient. The keratin expression profile showed the epithelial origin of the cell line, ploidy and karyotyping revealed the hyperdiploid population; ACSCC1 showed an increased tumorigenic and metastatic potential. Further, our cell line showed higher invasive, migratory potential and epithelial-mesenchymal-transition (EMT). Additionally, the Transmission electron microscopy (TEM) results showed an aberrant mitochondrial morphology and reduction in the cellular junctions. Further, our whole genome sequencing (WGS) analysis showed mutations in the cancer-related genes. Overall, the novel ACSCC1 cell line can be used to decipher the molecular signaling in the cancer stem cells (CSCs); targeting the CSCs population may help in understanding the tumor recurrence.

Real-time monitoring of fertilizer runoff at the watershed scale using a low-cost solar-powered Lego-like electrochemical water quality monitoring system - Muhammad Masud Rana; Sarath Gopalakrishnan; Akshay Krishnakumar; Sotoudeh Sedaghat; Devendra Sarnaik; Amin Zareei; Michael Douglas Ruffatti; Spencer Hagaman; Jason Lehto; Ali Shakouri; Shalamar Armstrong; Rahim Rahimi (Computers and Electronics in Agriculture, 2025)

Real-time six degrees of freedom grasping of deformable poultry legs in cluttered bins using deep learning and geometric feature extraction - Rekha Raja; Luis Angel Ponce Pacheco; Akshay K. Burusa; Gert Kootstra; Eldert Van Henten (Biosystems Engineering, 2025)

Improved charge carrier dynamics in rationally designed F-g-C3N4/In2O3 type II heterojunction for efficient pollutant removal: Mechanistic insights, real-world applications, and toxicity study - Arun S. Chopade; Akshay A. Ransing; Vinayak G. Parale; Santosh V. Mohite; Abhijit N. Kadam; Jiseung Kim; Vaishali A. Patil; Sadaf Jamal Gilani; Mohaseen S. Tamboli; Hyun-Kyung Kim; Dattakumar S. Mhamane; Hyung-Ho Park; et al. (Journal of Water Process Engineering, 2025)

Effect of UV-C LEDs and heat treatments on microbial safety, chemical and sensory properties of sweet lime juice - Akshay H. Dasalkar; Anisha Biswas; Sachin R. Chaudhari; Sudheer Kumar Yannam (Food Chemistry, 2025)

Lactose crystallization: Integrating machine learning with process analytical technologies - Cha Yong Jong; Akshay Mittal; Felix Jun Jie Lee; Lee May Loo; Yongkai Goh; Qiaolin Yuan; Eunice Wan Qi Yeap; Srinivas Reddy Dubbaka; Harsha Nagesh Rao; Shin Yee Wong (Food and Bioproducts Processing, 2025)

Bayesian-optimized recursive machine learning for predicting human-induced changes in suspended sediment transport - Soumya Kundu; Somil Swarnkar; Akshay Agarwal (Environmental Monitoring and Assessment, 2025)

Carboplatin Co-loaded 5-Fluorouracil Nanoparticles Conjugated with Trastuzumab for Targeted Therapy in HER2+ Heterogeneity Breast Cancer - Akshay Kumar Lunawat; Debanjan Mukherjee; Riya Shivgotra; Sarjana Raikwar; Ankit Awasthi; Amrinder Singh; Shamsher Singh; Shivani Chandel; Subheet Kumar Jain; Shubham Thakur (AAPS PharmSciTech, 2025)

Geospatial mapping and cluster analysis of antibiotic-resistant Escherichia coli in drinking water of semi-arid areas - Srishti Srivastava; Akshay Kumar; Rajiv Gupta; Abdul Malik (Environmental Monitoring and Assessment, 2025)

Assessing the Combined Toxicity of Silver and Copper Nanoparticles in Rainbow Trout (Oncorhynchus mykiss) Fingerlings - Saba Khursheed Khan; Joydeep Dutta; Mohd Ashraf Rather; Ishtiyaq Ahmad; Junaid Nazir; Showkat Shah; Suhas Ballal; Akshay Garg; Faisal Imam; Abhinav Kumar (Biological Trace Element Research, 2025)

Foam-Based Drug Delivery Systems for Skin Disorders: A Comprehensive Review - Syrsulu Myrzagulova; Zhexenova Azhar N; Mohit Kumar; Devesh Kumar; Akshay Kumar (AAPS PharmSciTech, 2025)

A new species of cyclophorid land snail (Caenogastropoda: Cyclophoridae) from the coastal regions of Maharashtra, India - Amrut Bhosale; Tejas Thackeray; Omkar Yadav; Akshay Khandekar; Tom S. White; Dinarzarde C. Raheem (Molluscan Research, 2025)

Deep learning based weed classification in corn using improved attention mechanism empowered by Explainable AI techniques - Akshay Dheeraj; Satish Chand (Crop Protection, 2025)

Multi-modal data fusion and deep ensemble learning for accurate crop yield prediction - Akshay Dagadu Yewle; Laman Mirzayeva; Oktay Karakuş (Remote Sensing Applications: Society and Environment, 2025)

Tolerance of Oryza sativa to low phosphate is associated with adaptive changes in root architecture and metabolic exudates - Akanksha Srivastava; Amber Gupta; Sujit K. Bishi; Pole Akhila; P.C. Latha; D. Subrahmanyam; P. Brajendra; M.S. Anantha; Suvarna Rani Ch; Akshay S. Sakhare; Vijai Pal Bhadana; Jitender Giri; et al. (Plant Science, 2025)

Comparative evaluation of needle-felt coir fibre with conventional media in treatment wetlands - Sanitha Gopalakrishnan; V.L. Aparna; Akshay D. Shende; Krishnakumar Bhaskaran (Journal of Water Process Engineering, 2025)

BpGDB: A genomic resource database of Bunium persicum for genetics and breeding - Akshay Singh; Nancy Sharma; Sangita Bansal; Rakesh Singh; G.P. Singh (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Advances in photocatalytic hydrogen production with ZnO/ZnS-Based nanostructured materials - Parul Rana; Vatika Soni; Rohit Kumar; Sonu; Akshay Chawla; Aftab Aslam Parwaz Khan; Pardeep Singh; Sourbh Thakur; Pankaj Raizada; Khalid A. Alzahrani (Fuel, 2025)

Evaluating the role of tree flora in air pollution mitigation and heavy metals accumulation near brick kilns - Akshay Kumar Singh; Subhalaxmi Behera; Jatin Kumar Choudhary; Sushil Kumar Shukla (Atmospheric Pollution Research, 2025)

Tailoring Drug Release Kinetics in Lipophilic Drug-Loaded Oral Microemulsions: Impact of Surfactant Chain Length - Himanshu Paliwal; Bhupendra G. Prajapati; Akshay Parihar; Mohammad Rashid Khan; Chetan Singh Chauhan (Journal of Pharmaceutical Innovation, 2025)

Characterising cowpea (Vigna unguiculata L. Walp) mini-core set for flowering responses to various photoperiod and temperature regimes - T. Lakshmi Pathy; A. Mohan Rao; T. V. Krishna; Kuldeep Tripathi; S. Ramesh; N. Akshay Rahul; Akshata G. Bhat; Pratibha B. Honnannavar (Genetic Resources and Crop Evolution, 2025)

A multi-aggregation approach to estimate avalanche vulnerability and suggest phase-wise adaptation - Akshay Singhal; M. Kavya; Sanjeev K. Jha (Environment, Development and Sustainability, 2025)

Phenyl-bridged silica aerogels with enhanced textural and mechanical properties for heavy metal removal - Qi Wang; Akshay A. Ransing; D.B. Mahadik; Puttavva Meti; Haryeong Choi; Taehee Kim; Hyung-Ho Park (Journal of Water Process Engineering, 2025)

Ionotropically-engineered synthesis of mechanically robust hybrid sodium alginate–silica aerogels with enhanced specific surface area for high-capacity and selective dye adsorption from wastewater - Akshay A. Ransing; Qi Wang; Rushikesh P. Dhavale; Haryeong Choi; Uzma K.H. Bangi; Vinayak G. Parale; Wonjun Lee; Kazuyoshi Kanamori; Hyung-Ho Park (Chemical Engineering Journal, 2025)

Exploration of Anomuran Crabs from the Intertidal zone of Kadmat and Amini Islands of the Lakshadweep Archipelago, India - Naseem N. M.; Jayalakshmi K. J; Davood Nihal; Akshay A. Kumar (Thalassas: An International Journal of Marine Sciences, 2025)

Dual-nutrient stress tolerance in wheat is regulated by nitrogen and phosphorus uptake, assimilation, reutilization, and differential expression of candidate genes - Renu Pandey; Sandeep Sharma; Ankita Mishra; Akshay Sureshrao Sakhare; Surendra Kumar Meena; Krishnapriya Vengavasi (Plant and Soil, 2025)

Influence of zeolite additives and an innovative accelerated carbonation technique on the mechanical and corrosion properties of carbonated concrete - Akshay Ramesh Bura; B. Kondraivendhan (Innovative Infrastructure Solutions, 2025)

Geological and Cultural Heritage of Lithic Artefacts Unearthed from Fort Kochi, Southern India - R. T. Ratheesh-Kumar; B. Uthara; V. S. Duniya Raj; B. Devati; P. B. Akshay (Geoheritage, 2025)

Exploration of Abiraterone acetate loaded Nanostructured lipid carriers for bioavailability improvement and circumvention of fast-fed variability - Saurabh Shah; Paras Famta; Ganesh Vambhurkar; Abhishek Sharma; Atul Mourya; Dadi A. Srinivasarao; Akshay Shinde; Sajja Bhanu Prasad; Giriraj Pandey; Jitender Madan; Saurabh Srivastava (Drug Delivery and Translational Research, 2025)

Transdermal delivery of resveratrol loaded solid lipid nanoparticle as a microneedle patch: a novel approach for the treatment of Parkinson’s disease - Akshay Bandiwadekar; Jobin Jose; Gopika Gopan; Varsha Augustin; Harsha Ashtekar; Kartik Bhairu Khot (Drug Delivery and Translational Research, 2025)

Agroecosystem contamination with heavy metals due to road transportation: A global threat to safe food security - Akshay Kumar Singh; Jatin Kumar Choudhary; Sushil Kumar Shukla; Kuldeep Bauddh; Gavendra Pandey; Sughosh Madhav; Ajai Singh; Manoj Kumar (Process Safety and Environmental Protection, 2025)

Heat transfer in large bins during the apples cool-down process - Tuany Gabriela Hoffmann; Manfred Linke; Ulrike Praeger; Akshay D. Sonawane; Felix Büchele; Daniel Alexandre Neuwald; Reiner Jedermann; Barbara Sturm; Pramod V. Mahajan (International Journal of Refrigeration, 2025)

An Imprecise Hybrid Reliability Methodology for Rock Structures Considering Spatial Variations of Inputs with Mixed Uncertainties: Theory and Application - Surabhi Maurya; Akshay Kumar; Gaurav Tiwari (Computers and Geotechnics, 2025)

CRISPR/Cas12a mediated rapid and efficient detection of Tomato Leaf Curl Karnataka Virus without amplification - Thalooru Shashikala; Dhawane Yogi; Kumar Akshay; Karuppannasamy Ashok; Somakalahalli Narasimhappa Nagesha; Maligeppagol Manamohan; Girish Kumar Jha; Ramasamy Asokan (Biocatalysis and Agricultural Biotechnology, 2025)

CRISPR-Cas technology: an emerging opportunity for precise identification of diseases in plants - C. Shanmugaraj; H. M. Akshay Kumar; V. Jaiganesh; M. K. Biswas; R. Gangaraj (Journal of Plant Diseases and Protection, 2025)

Amelioration of breast cancer therapies through normalization of tumor vessels and microenvironment: paradigm shift to improve drug perfusion and nanocarrier permeation - Paras Famta; Saurabh Shah; Ganesh Vambhurkar; Giriraj Pandey; Deepkumar Bagasariya; Kondasingh Charan Kumar; Sajja Bhanu Prasad; Akshay Shinde; Suraj Wagh; Dadi A. Srinivasarao; Rahul Kumar; Dharmendra Kumar Khatri; et al. (Drug Delivery and Translational Research, 2025)

Flash Drought Teleconnection With the Large‐Scale Climate Drivers in the Homogeneous Rainfall Regions of India - Akshay Pachore; Renji Remesan; Jayanarayanan Kuttippurath (International Journal of Climatology, 2025)
Flash drought events can be characterised by the quick depletion of crop root zone soil moisture (rapid intensification) and hence can be termed as agricultural flash droughts. These events can have devastating impacts, such as increasing the risk of agricultural yield loss, heatwaves and increased wildfire risk, which further have cascading impacts on the socio‐economic conditions. The regional hotspots of flash droughts are analysed for winter, pre‐monsoon, monsoon and post‐monsoon seasons over India from 1981 to 2020. We assess the impact of the El Niño‐Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) on the flash drought frequency (FDF: number of flash drought events). The causal connection of the FDF with the ENSO and IOD is analysed using the PCMCI (Peter and Clark's algorithm combined with the Momentary Conditional Independence) algorithm. The monsoon season (June–September) is found to be more prone to flash droughts with higher spatial/regional average values of total per pixel FDF during the 40‐year period over the Central Northeast (~54) and West Central (~41) regions. It is observed that the fraction of the total number of flash droughts during the El Niño years (38.8%) is higher as compared with that in La Niña years (25.7%). It is also found that the co‐occurrence of positive/negative IOD with the El Niño phase can alter the seasonal fraction of FDF over India, highlighting the high complexity in the ENSO–IOD interactions. The causal analysis shows that only the Southern Peninsula and West Central regions have significant direct and lagged causal links of average per pixel FDF with IOD. Whereas, similar (direct and lagged) causal connections are observed between the ENSO and IOD. This study reveals that flash droughts and their teleconnections vary greatly among the seasons and regions in India, limiting its accurate predictions and increasing the risk to agricultural communities.

Appropriate Fire Intensity Measures for Reinforced Concrete Beam and Column Elements - Akshay Baheti; David Lange; Vasant Matsagar (Engineering Structures, 2025)

Sol-gel synthesized homogeneous nanofibers to multidimensional in-situ and ex-situ silica nanofiber aerogels in thermal management applications - Rushikesh P. Dhavale; Vinayak G. Parale; Haryeong Choi; Taehee Kim; Akshay A. Ransing; Varsha D. Phadtare; Kyu-Yeon Lee; Hyung-Ho Park (Chemical Engineering Journal, 2025)

Investigating role of corn stover biochar supplementation on continuous pilot scale anaerobic digestion: Performance and microbial community dynamics - Sachin Krushna Bhujbal; Preeti; Akshay Joshi; Pooja Ghosh; Virendra Kumar Vijay (Bioresource Technology, 2025)

Pressure Drop and Interfacial Heat Transfer Coefficient Formulation for Packed Bed Systems with Cylindrical Capsules - Akshay Kumar; Pratyush Kumar; Sandip K. Saha (Transport in Porous Media, 2025)

Influence of Microenvironmental Orchestration on Multicellular Lung Alveolar Organoid Development from Human Induced Pluripotent Stem Cells - Vedat Burak Ozan; Huijuan Wang; Akshay Akshay; Deepika Anand; Youssef Hibaoui; Anis Feki; Janine Gote-Schniering; Ali Hashemi Gheinani; Manfred Heller; Anne-Christine Uldry; Sophie Braga Lagache; Amiq Gazdhar; et al. (Stem Cell Reviews and Reports, 2025)
Induced pluripotent stem cells (iPSCs) have emerged as promising in vitro tools, providing a robust system for disease modelling and facilitating drug screening. Human iPSCs have been successfully differentiated into lung cells and three-dimensional lung spheroids or organoids. The lung is a multicellular complex organ that develops under the symphonic influence of the microenvironment. Here, we hypothesize that the generation of lung organoids in a controlled microenvironment (cmO) (oxygen and pressure) yields multicellular organoids with architectural complexity resembling the lung alveoli. iPSCs were differentiated into mature lung organoids following a stepwise protocol in an oxygen and pressure-controlled microenvironment. The organoids developed in the controlled microenvironment displayed complex alveolar architecture and stained for SFTPC, PDPN, and KRT5, indicating the presence of alveolar epithelial type II and type I cells, as well as basal cells. Moreover, gene and protein expression levels were also increased in the cmO. Furthermore, pathway analysis of proteomics revealed upregulation of lung development-specific pathways in the cmO compared to those growing in normal culture conditions. In summary, by using a controlled microenvironment, we established a complex multicellular lung organoid derived from iPSCs as a novel cellular model to study lung alveolar biology in both lung health and disease. Graphical Abstract

Quality by design empowered preparation of itraconazole albumin nanoparticles for prostate cancer - Saurabh Shah; Paras Famta; Anamika Sharma; Rahul Kumar; Giriraj Pandey; Ganesh Vambhurkar; Dadi A. Srinivasarao; Akshay Shinde; Sajja Bhanu Prasad; Amit Asthana; Saurabh Srivastava (Drug Delivery and Translational Research, 2025)

Impact of MY-1 and Enterotrophotic as probiotics on growth and survival of Macrobrachium rosenbergii post-larvae during pre- and post-challenge with Vibrio alginolyticus - Vinusree K.P.; Diya Dominic D.V.; Ramya R. Nair; Riya George; Rosamma Philip; Muneer A.; Akshay P.S.; I. S. Bright Singh (Aquaculture International, 2025)

Genome-wide association study on root traits under non-stress and osmotic stress conditions to improve drought tolerance in rice (Oryza sativa Lin.) - Akshay Sureshrao Sakhare; Sudhir Kumar; Ranjith K. Ellur; G. D. Prahalada; Suneetha Kota; Ranjeet Ranjan Kumar; Soham Ray; Baidya Nath Mandal; Viswanathan Chinnusamy (Acta Physiologiae Plantarum, 2025)

A Hemicyanin-Based Water-Soluble off-on Fluorescence and Colorimetric Probe for Detecting HSO3−/SO32− in Real Samples - Akshay Kodiyawala; Sahil Kiroriwal; Suban K. Sahoo; Tapas Ghatak; Subrata Dutta (Journal of Fluorescence, 2024)

Semantics-aware next-best-view planning for efficient search and detection of task-relevant plant parts - Akshay K. Burusa; Joost Scholten; Xin Wang; David Rapado-Rincón; Eldert J. van Henten; Gert Kootstra (Biosystems Engineering, 2024)

Current status of mangrove conservation efforts in Qatar: A review - Pavithra S. Pitumpe Arachchige; Marcela Rondon; Abhilash Dutta Roy; Michael S. Watt; Mollie Davies; Dhouha Ouerfelli; Ewane Basil Ewane; Ammar Abulibdeh; Meshal Abdullah; Talal Al-Awadhi; Akshay Sharma; Ricardo Martínez Prentice; et al. (Regional Studies in Marine Science, 2024)

Spatially explicit simulation and forecasting of urban growth using weights of evidence based cellular automata model in a millennium city of India - Pankaj Kumar Yadav; Varun Narayan Mishra; Maya Kumari; Akshay Kumar; Pradeep Kumar; Rajeev Bhatla (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Nanotechnology: An emerging trend in the dairy industry – Applications and future challenges - Akshay Ramani; Sathiya Taherabbas; Rakendhu Saji; Mitul Bumbadiya; Kamal Gandhi; Raman Seth (Food and Humanity, 2024)

Assessing dynamics of urban solar PV power generation using grid divisional method - Akshay Kaleshwarwar; Sarika Bahadure (Energy and Buildings, 2024)

Role of important physiological traits and development of heat tolerance index in a large set of diverse cucumber germplasm - Dhananjay A. Hongal; A. D. Munshi; Akshay Talukdar; Anjan Das; N. Pradeepkumara; M. Karthik Kumar; Jyoti Kumari; Viswanathan Chinnusamy; J. K. Ranjan; T. K. Behera; S. S. Dey (Acta Physiologiae Plantarum, 2024)

MicroRNA Guided In Silico Drug Repositioning for Malaria - Sowmya R. Prabhu; Akshay Pramod Ware; Kapaettu Satyamoorthy; Abdul Vahab Saadi (Acta Parasitologica, 2024)

Alkaloid-rich fraction of Anacardium occidentale L. nutshells ameliorates UV-B induced oxidative damage in human peripheral blood mononuclear cells - Arti Dilip Pol; Pallavi Jayant Wankhede; Akshay Dilip Bagwe; Bharatbhushan Sharma (Vegetos, 2024)

Development of 1 ×1 km gridded emission inventory for air quality assessment and mitigation strategies from open biomass burning in Karnataka, India - Narayan Kayet; Tejaswini Eregowda; Likitha M P; Akshay Kumar V Ganeshker; Geeta Hegde (Urban Climate, 2024)

Taking the wheel: Systematic review of reviews of policies driving BEV adoption - V. Anilan; Akshay Vij (Transportation Research Part D: Transport and Environment, 2024)

Multi-gene phylogeny and phenotypic analyses revealed an association of different Colletotrichum species with inflorescence dieback and leaf spot of arecanut in India - V.H. Prathibha; M.K. Rajesh; Akshay Dinesh; Balanagouda Patil; Daliyamol; N.R. Nagaraja; Rajkumar; A.A. Sabana; K.P. Gangaraj; K.P. Thejasri; Sunil S. Gangurde; Vinayaka Hegde (Physiological and Molecular Plant Pathology, 2024)

Adaptive (re)operations facilitate environmental flow maintenance downstream of multi-purpose reservoirs - Akshay Sunil; Riddhi Singh; Manvitha Molakala (Journal of Hydrology, 2024)

Outcrop analogue constraints on subsurface reservoir properties of the Puga geothermal field, NW Himalaya - Samuel T. Thiele; Horthing V. Zimik; Anindita Samsu; Salim Akhtar; Akshay Kamath; Pankaj Khanna (Geothermics, 2024)

Does the rate of metal salt precursor addition during ZIF-8 nanoparticles preparation affect their morphology?: Application in dye adsorption - Animesh Jana; A. Vijayalakshmi; Suganesh Raghunathan; Aishwarya Shankar; Krishnamurthy Sainath; Akshay Modi (Colloids and Surfaces C: Environmental Aspects, 2024)

Attention-driven next-best-view planning for efficient reconstruction of plants and targeted plant parts - Akshay K. Burusa; Eldert J. van Henten; Gert Kootstra (Biosystems Engineering, 2024)

Can pyrolysis handle biomedical wastes?: Assessing the potential of various biomedical waste treatment technologies in tackling pandemics - Akshay Srivastava; Anita Sharma; Manoj Kumar Jena; Arun K. Vuppaladadiyam; Febelyn Reguyal; Jyeshtharaj Joshi; Abhishek Sharma; Kalpit Shah; Akhilendra Gupta; Bridgid Lai Fui Chin; Agus Saptoro; Ajit K. Sarmah (Science of The Total Environment, 2024)

CuS modified graphite from spent Li-ion batteries towards building high energy Na-ion capacitors via solvent-co-intercalation process - Manohar Akshay; Shaji Jyothilakshmi; Yun-Sung Lee; Vanchiappan Aravindan (Chemical Engineering Journal, 2024)

Unlocking the potential of Mg-ion batteries: Cu2C MXene anode with ultrahigh storage and energy density with rapid Mg diffusion - Gaushiya A. Shaikh; Akshay M. Satawara; Sanjeev K. Gupta; P.N. Gajjar (Chemical Engineering Journal, 2024)

A top-down spatial scenario approach for identifying the locations of rainwater harvesting sites in an urban region - Gaurav Kumar; Deshbhushan Patil; Akshay Kumar; Rajiv Gupta (Environmental Science and Pollution Research, 2024)

Unveiling heavy metal pollution dynamics in sediments of river Ulhas, Maharashtra, India: a comprehensive analysis of anthropogenic influence, pollution indices, and health risk assessment - Akshay Botle; Sayli Salgaonkar; Rahul Tiwari; Gayatri Barabde (Environmental Geochemistry and Health, 2024)

Evaluation of the proximate composition and antioxidant capacity of some seaweeds from the Konkan coast of India - T.E.M.J.E.N.S.A.N.G.B.A. IMCHEN; K.O.N.A.R.K. TRIPATHI; R.E.S.H.M.I.T.H.A. RAMAKRISHNAN; K.R.I.S.H.N.A. P. AKSHAY (Algal Research, 2024)

Combining global precipitation data and machine learning to predict flood peaks in ungauged areas with similar climate - Zimeena Rasheed; Akshay Aravamudan; Xi Zhang; Georgios C. Anagnostopoulos; Efthymios I. Nikolopoulos (Advances in Water Resources, 2024)

Identification and evaluation of multi-antigenic epitopes of immunodominant protein from the selected Crimean–Congo hemorrhagic fever virus genome towards the development of diagnostic and vaccine candidates by reverse vaccinology approach - Akshay Jeyachandran; Reshma Muthuvel; Selvaraj Jagannathan; Sarika Baburajan Pillai; Vijayakumar Rajendran; Rahul Gandhi Pachamuthu; Ajithkumar Balakrishnan; Hemamalini Vedagiri; Shivanandappa Kukkaler Channappa; Ananda Arona Premkumar; Sivakumar Sakthivel; Abhishek Mandal (Journal of Proteins and Proteomics, 2024)

Reliability analysis of deep tunnels in spatially varying brittle rocks using interval and random field modelling - Akshay Kumar; Surabhi Maurya; Gaurav Tiwari (International Journal of Rock Mechanics and Mining Sciences, 2024)

Impact of UV-C treatment on the inactivation of microbes and amino acid composition in cow milk and buffalo milk: A comparative study - Akshay H. Dasalkar; Raj Kumar Maguluri; Salony Raghunath Vaishnav; Sridevi Annapurna Singh; Sudheer Kumar Yannam (International Dairy Journal, 2024)

A feasibility study on femtosecond laser texturing of sprayed nanocellulose coatings - Pieter Samyn; Joris Everaerts; Akshay Mundayadan Chandroth; Patrick Cosemans; Olivier Malek (Carbohydrate Polymers, 2024)

Modified speed breeding approach reduced breeding cycle to less than half in vegetable soybean [Glycine max (L.) Merr.] - Meniari Taku; Manisha Saini; Rahul Kumar; Pulak Debbarma; Nenavath Krishna Kumar Rathod; Reshma Onteddu; Deepshikha Sharma; Renu Pandey; Kishore Gaikwad; S. K. Lal; Akshay Talukdar (Physiology and Molecular Biology of Plants, 2024)

Consequences of Local Conspecific Density Effects for Plant Diversity and Community Dynamics - Joseph A. LaManna; Florian Hartig; Jonathan A. Myers; Robert P. Freckleton; Matteo Detto; Akshay Surendra; Cole J. Doolittle; Bénédicte Bachelot; Robert Bagchi; Liza S. Comita; David M. DeFilippis; Nohemi Huanca‐Nunez; et al. (Ecology Letters, 2024)
Conspecific density dependence (CDD) in plant populations is widespread, most likely caused by local‐scale biotic interactions, and has potentially important implications for biodiversity, community composition, and ecosystem processes. However, progress in this important area of ecology has been hindered by differing viewpoints on CDD across subfields in ecology, lack of synthesis across CDD‐related frameworks, and misunderstandings about how empirical measurements of local CDD fit within the context of broader ecological theories on community assembly and diversity maintenance. Here, we propose a conceptual synthesis of local‐scale CDD and its causes, including species‐specific antagonistic and mutualistic interactions. First, we compare and clarify different uses of CDD and related concepts across subfields within ecology. We suggest the use of local stabilizing/destabilizing CDD to refer to the scenario where local conspecific density effects are more negative/positive than heterospecific effects. Second, we discuss different mechanisms for local stabilizing and destabilizing CDD, how those mechanisms are interrelated, and how they cut across several fields of study within ecology. Third, we place local stabilizing/destabilizing CDD within the context of broader ecological theories and discuss implications and challenges related to scaling up the effects of local CDD on populations, communities, and metacommunities. The ultimate goal of this synthesis is to provide a conceptual roadmap for researchers studying local CDD and its implications for population and community dynamics.

RETRACTED: Levothyroxine synthesis impurities are neither mutagenic nor genotoxic: Insilico, Ames test and micronucleus test studies - Rajesh Rane; Akshay Prabhune; Dileep Kumar; Ajay Kumar; Madhur Sewlikar; Mugdha Suryawanshi; Bharat Satpute; Bapu Gawade; Sachin Sakat (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

An overview of heavy metals treatment & management for laboratory waste liquid (LWL) - Swati P. Dhenkula; Akshay D. Shende; Leena Deshpande; Girish R. Pophali (Journal of Environmental Chemical Engineering, 2024)

Recent advances in synthesis methods and surface structure manipulating strategies of copper selenide (CuSe) nanoparticles for photocatalytic environmental and energy applications - Akshay Chawla; Anita Sudhaik; Sonu; Rohit Kumar; Pankaj Raizada; Aftab Aslam Parwaz Khan; Tansir Ahamad; Van-Huy Nguyen; Rangabhashiyam Selvasembian; Ajeet Kaushik; Pardeep Singh (Journal of Environmental Chemical Engineering, 2024)

Nanofabrication of citronellal with chitosan biopolymer to boost its efficacy against aflatoxin B1 and Aspergillus flavus mediated biodeterioration of active ingredient of Piper longum - Akshay Kumar; Tanya Singh Raghuvanshi; Surya Pratap; Horesh Kumar; Bhanu Prakash (Food Chemistry, 2024)

Oral administration of recombinant outer membrane protein A-based nanovaccine affords protection against Aeromonas hydrophila in zebrafish - Mave Harshitha; Ruveena D’souza; Sadanand Dangari Akshay; Ashwath Nayak; Somanath Disha; Vankadari Aditya; Uchangi Satyaprasad Akshath; Saurabh Dubey; Hetron Mweemba Munang’andu; Anirban Chakraborty; Indrani Karunasagar; Biswajit Maiti (World Journal of Microbiology and Biotechnology, 2024)

CmirC update 2024: a multi-omics database for clustered miRNAs - Akshay Pramod Ware; Kapaettu Satyamoorthy; Bobby Paul (Functional & Integrative Genomics, 2024)
Clustered miRNAs consist of two or more miRNAs transcribed together and may coordinately regulate gene expression. Differential expression of clustered miRNAs is found to be controlled by crosstalk of genetic or epigenetic mechanisms. It has been demonstrated that clustered miRNA expression patterns greatly impact cancer cell progression. With the CmirC initiative, we initially developed a comprehensive database to identify copy number variation (CNV) driven clustered miRNAs in cancer. Now, we extended the analysis and identified three miRNAs, mir-96, mir-183, and mir-21, were found to be significantly upregulated in 17 cancer types. Further, CmirC is now upgraded to determine the impact of changes in the DNA methylation status at clustered miRNAs by utilizing The Cancer Genomic Atlas (TCGA) cancer datasets. We examined specific methylation datasets from 9,639 samples, pinpointing 215,435 methylation sites and 27,949 CpG islands with miRNA cluster information. The integrated analysis identified 34 clusters exhibiting differentially methylated CpG sites across 14 cancer types. Furthermore, we determined that CpG islands in the promoter region of 20 miRNA clusters could play a regulatory role. Along with ensuring a straightforward and convenient user experience, CmirC has been updated with improved data browsing and analysis functionalities, as well as enabled hyperlinks to literature and miR-cancer databases. The enhanced version of CmirC is anticipated to play an important role in providing information on the regulation of clustered miRNA expression, and their targeted oncogenes and tumor suppressors. The newly updated version of CmirC is available at https://slsdb.manipal.edu/cmirclust/ .

Assessing dual resistance to stripe rust and powdery mildew in wheat germplasm through molecular and field studies across the north-western Himalayas - Shubham Verma; Harinder K. Chaudhary; Anila Badiyal; Kritika Singh; Kulveer Singh Dhillon; Akshay Pathania; Mukul Sharma (Euphytica, 2024)

Erratum to: Exploring Dragon Fruit in India: From Taxonomy to Nutritional Benefits and Sustainable Cultivation Practices - Abeer Ali; Akshay Dhillon; Nimisha Sharma; Chandana M.R.; Menaka M.; Pradeep Kumar Vishwakarma; Dhrumeshkumar Chavda (Applied Fruit Science, 2024)

Exploring Dragon Fruit in India: From Taxonomy to Nutritional Benefits and Sustainable Cultivation Practices - Abeer Ali; Akshay Dhillon; Nimisha Sharma; Chandana M.R.; Menaka M.; Pradeep Kumar Vishwakarma; Dhrumeshkumar Chavda (Applied Fruit Science, 2024)

3D pose estimation of tomato peduncle nodes using deep keypoint detection and point cloud - Jianchao Ci; Xin Wang; David Rapado-Rincón; Akshay K. Burusa; Gert Kootstra (Biosystems Engineering, 2024)

The where, when, and how of ooid formation: What ooids tell us about ancient seawater chemistry - Bolton Howes; Akshay Mehra; Emily Geyman; Julia Wilcots; Ryan Manzuk; Curtis Deutsch; Adam Maloof (Earth and Planetary Science Letters, 2024)

Spatiotemporal retrieval of the aerosol optical thickness using Landsat 8 OLI imagery for Indian urban area - Akshay Chauhan; Namrata Jariwala; Robin Christian (Air Quality, Atmosphere & Health, 2024)

Aerosols and black carbon variability using OMI and MERRA-2 and their relationship to near-surface air temperature - Akshay Chauhan; Namrata Jariwala; Robin Christian (Environmental Science and Pollution Research, 2024)

Exploring the depths: Metagenomic profiling of cold seep bacterial communities and isolation of hydrocarbon-degrading microbes from the Cauvery-Mannar basin - Akshay Unnikrishnan; Priyanka Das; Narsinh L. Thakur; Prabha Devi (Regional Studies in Marine Science, 2024)

Assessment of Trachyspermum ammi essential oil against Aspergillus flavus, aflatoxin B1 contamination, and post-harvest quality of Sorghum bicolor - Prem Pratap Singh; Atul Kumar Jaiswal; Ritu Singh; Akshay Kumar; Vishal Gupta; Tanya Singh Raghuvanshi; Angad Sharma; Bhanu Prakash (Food Chemistry, 2024)

Harnessing dimethyl ether with ultra-low-grade heat for scaling-resistant brine concentration and fractional crystallization - Zi Hao Foo; Akshay Deshmukh; Aaron D. Wilson; John H. Lienhard (Chemical Engineering Journal, 2024)

LWDN: lightweight DenseNet model for plant disease diagnosis - Akshay Dheeraj; Satish Chand (Journal of Plant Diseases and Protection, 2024)

Key physiological traits for drought tolerance identified through phenotyping a large set of slicing cucumber (Cucumis sativus L.) genotypes under field and water-stress conditions - Anjan Das; A. D. Munshi; Dhandapani Raju; Sudhir Kumar; Dharmendara Singh; Akshay Talukdar; Dhananjay Hongal; Mir Asif Iquebal; Sandeep Kumar; R. C. Bhattacharya; Pragya Ranjan; Oula Ghannoum; et al. (Genetic Resources and Crop Evolution, 2024)

Variability of low-level jet over the Arabian Sea and its association with Indian summer monsoon rainfall - Archana Sagalgile; P. V. S. Raju; Akshay Kulkarni; Jagdish Prasad; V. B. Rao; Suvarna Fadnavis (Climate Dynamics, 2024)

Activated platelet-rich plasma accelerate endometrial regeneration and improve pregnancy outcomes in murine model of disturbed endometrium - Jeevitaa Kshersagar; Akshay A. Kawale; Kishor Tardalkar; Mrunal N. Damle; Leena R. Chaudhari; Rakesh Sharma; Meghnad G. Joshi (Cell and Tissue Banking, 2024)

Spatio-Temporal Dynamics of Aerosol Optical Thickness derived Using MODIS-MAIAC Algorithm at a High Spatial Resolution Along with the HYSPLIT Trajectory Model - Akshay C. Chauhan; Namrata D. Jariwala; Robin A. Christian (Aerosol Science and Engineering, 2024)

Nitrate removal from contaminated groundwater by micellar-enhanced ultrafiltration using a polyacrylonitrile membrane with a hydrogel-stabilized ZIF-L layer - Akshay Modi; Roni Kasher (Water Research, 2024)

One pot synthesis of multi-functional B doped g-C3N4-praseodymium oxide nanocomposites for colorimetric detection of Hg2+ ion and solar photocatalytic removal of toxic water pollutants - Vandana Sairaj; Akshay Sidhi Poovethamkandiyil; S. Anas; Steve J. Hinder; Suresh C. Pillai; Baiju Kizhakkekilikoodayil Vijayan (Journal of Water Process Engineering, 2024)

APC2Mesh: Bridging the gap from occluded building façades to full 3D models - Perpetual Hope Akwensi; Akshay Bharadwaj; Ruisheng Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Process-structure-function relationship for mamaku suspension: Effect of drying methods on powder functionality - Akshay Bisht; Kelvin K.T. Goh; Lara Matia-Merino (Food Hydrocolloids, 2024)

Application of FTIR spectroscopy in dairy products: A systematic review - Rakendhu Saji; Akshay Ramani; Kamal Gandhi; Raman Seth; Rajan Sharma (Food and Humanity, 2024)

Emerging potential of whey proteins in prevention of cancer - Akshay Ramani; Tanmay Hazra; Sheweta Mudgil; Deepak Mudgil (Food and Humanity, 2024)

Carnelian beads from Manda, Unguja Ukuu and Kwa Mgogo: New insights on the stone bead trade between South Asia and East Africa, 7th to 15th Century CE - Jonathan Mark Kenoyer; Chapurukha M. Kusimba; Akshay Sarathi; Jonathan R. Walz; Randall W. Law; Laure Dussubieux (Archaeological and Anthropological Sciences, 2024)

Seasonal diversity and abundance distribution of butterflies in Dihing Patkai national park, North East India - Prasun Karmakar; Dhrubajyoti Das; Akshay Mishra; Gauri Bharadwaj; Chandan Borah (International Journal of Tropical Insect Science, 2024)

Phytoremediation: An emerging green technology for dissipation of PAHs from soil - Harleen Kaur; Akshay Kumar; Shayla Bindra; Ashish Sharma (Journal of Geochemical Exploration, 2024)

Strength, deformation, and environmental impact assessment of cement stabilized mine overburden soil - Anshumali Mishra; Akshay Dixit; Avinash Kumar Singh; Sarat Kumar Das (Journal of Cleaner Production, 2024)

Needle-Felt Coir fibre: A natural substitute for synthetic media in anaerobic fixed film reactors for wastewater treatment - Sanitha Gopalakrishnan; R.S. Dipin Nath; Akshay D. Shende; Krishnakumar Bhaskaran (Journal of Environmental Chemical Engineering, 2024)

Pressure exchanger batch reverse osmosis with zero downtime operation - Abhimanyu Das; Akshay K. Rao; Sultan Alnajdi; David M. Warsinger (Desalination, 2024)

Does harvesting age matter? Changes in structure and rheology of a shear-thickening polysaccharide from Cyathea medullaris as a function of age - Akshay Bisht; Kelvin K.T. Goh; Ian M. Sims; Patrick J.B. Edwards; Lara Matia-Merino (Carbohydrate Polymers, 2024)

Evaluating the sensitivity of fine particulate matter (PM2.5) simulations to chemical mechanism in WRF-Chem over Delhi - Rajmal Jat; Chinmay Jena; Prafull P. Yadav; Gaurav Govardhan; Gayatry Kalita; Sreyashi Debnath; Preeti Gunwani; Prodip Acharja; PoojaV. Pawar; Pratul Sharma; Santosh H. Kulkarni; Akshay Kulkarni; et al. (Atmospheric Environment, 2024)

Comparative study of different strengthening methods on the RC columns exposed to high temperatures - A. B. Danie Roy; Asif H. Shah; Akshay Sharma; C. Shermi (Innovative Infrastructure Solutions, 2024)

Recent Trends in Nanocarrier-Based Drug Delivery System for Prostate Cancer - Amit Kumar; Akshay Kumar Lunawat; Ashutosh Kumar; Tarun Sharma; Md Moidul Islam; Milan Singh Kahlon; Debanjan Mukherjee; Raj Kumar Narang; Sarjana Raikwar (AAPS PharmSciTech, 2024)

Microplastic pollutants in water: A comprehensive review on their remediation by adsorption using various adsorbents - Akshay Verma; Gaurav Sharma; Amit Kumar; Pooja Dhiman; Genene Tessema Mola; Ali Shan; Chuanling Si (Chemosphere, 2024)

Seafood processing waste as a source of functional components: Extraction and applications for various food and non-food systems - D.S. Akhila; Priyanka Ashwath; Kavitha Guladahalli Manjunatha; Sadanand Dangari Akshay; Vijay Kumar Reddy Surasani; Faisal Rashid Sofi; Kawkabul Saba; Pavan Kumar Dara; Yesim Ozogul; Fatih Ozogul (Trends in Food Science & Technology, 2024)

A model integrating fruit physiology, perforation, and scavenger for prediction of ethylene accumulation in fruit package - Akshay D. Sonawane; Saowapa Chaiwong; Cornelia Weltzien; Pramod V. Mahajan (Postharvest Biology and Technology, 2024)

Comparative analytical analysis and component selection of resistojet thruster for satellite propulsion - Aswin M R; Akshay Pavithran; Yash Mangrole; Shriya Shivaraman; Chinmay Sanjay Kulaye; Amit Kumar Thakur; Balaji R (Journal of Space Safety Engineering, 2024)

Investigation of alpha amylase inhibitors from Bidens pilosa L. by in silico and in vitro studies - Akshay Galagali; Vishal S. Patil; Kashinath Hiremath; Ganesh H. Sampat; Rajlaxmi Patil; Rajashri Virge; Darasaguppe R. Harish; Harsha V. Hedge; Subarna Roy (In Silico Pharmacology, 2024)

Dynamics of unipolar charged particles flowing through a cylindrical tube at high number concentrations - Akshay Shridhar Kale; Mino Woo; Jacob J. Swanson; Dong-Ha Lim; Adam M. Boies (Journal of Aerosol Science, 2024)

A study on speciation and enrichment of rare earth elements (REE) by sequential extraction from a potential coal fly ash resource and its role in REE extractability - Akshay Kumar Singh Choudhary; Santosh Kumar; Sudip Maity (Hydrometallurgy, 2024)

‛Trophic switch’ by catfish community from predation to scavenging modulated by human food discard in an estuarine bay - Deepa Shashikant Yogi; Akshay Naik; Ranjana Yadav; Aniket Desai; Mandar Nanajkar (Environmental Science and Pollution Research, 2024)

A facile approach for oil-water separation using superhydrophobic polystyrene-silica coated stainless steel mesh bucket - Rajaram S. Sutar; Sanjay S. Latthe; Akshay R. Jundle; Pradip P. Gaikwad; Sagar S. Ingole; Saravanan Nagappan; Yong Hyun Kim; Appasaheb K. Bhosale; Viswanathan S. Saji; Shanhu Liu (Marine Pollution Bulletin, 2024)

Therapeutic applications of canine platelets and their derivatives: a narrative review - Deeksha Bharti; Y. Ajith; Khan Sharun; S. Amitha Banu; Akshay Kumar; Abhishek Bhardwaj; Shiv Kumar Sidar; Dhaleshwari (Topics in Companion Animal Medicine, 2024)

Condensation particle counters: Exploring the limits of miniaturisation - Shaamrit Balendra; Akshay Kale; Julie Pongetti; Mohsen Kazemimanesh; Molly Haugen; Lee Weller; Adam Boies (Journal of Aerosol Science, 2024)

Identifying Potential Locations of Hydrologic Monitoring Stations Based on Topographical and Hydrological Information - Akshay Singhal; Muhammed Jaseem; Divya; Shiblu Sarker; Pragati Prajapati; Ankit Singh; Sanjeev K. Jha (Water Resources Management, 2024)

Selection of elite genotypes deploying AMMI, GGE and MTSI in okra [Abelmoschus esculentus (L.) Moench] - Arpita A. Patel; Rajesh D. Vekariya; Rumit Patel; Akshay Patel (South African Journal of Botany, 2023)

Finfish fishery of Ashtamudi Estuary, India- A Ramsar site of International significance - Akshay .A. Kumar; Anvar Ali P.H.; Sreekanth Giri Bhavan (Regional Studies in Marine Science, 2023)

Energy, exergy and emission [3E] analysis of Mesua Ferrea seed oil biodiesel fueled diesel engine at variable injection timings - Akshay Jain; Bhaskor Jyoti Bora; Rakesh Kumar; Prabhakar Sharma; Bhaskar Jyoti Medhi; Gottipati Venkata Rambabu; Balakrishnan Deepanraj (Fuel, 2023)

Simultaneous determination of three curative flavonoids and neurotoxic anisatin in star anise fruits by ultra-high performance liquid chromatography-tandem mass spectrometry - Akshay Suresh Patil; Xingyu Li; Yan Xu (Food Chemistry, 2023)

Shear and temperature sensitivity of a shear-thickening biopolymer from the New Zealand black tree fern - Akshay Bisht; Kelvin K.T. Goh; Ian M. Sims; Patrick J.B. Edwards; Lara Matia-Merino (Food Hydrocolloids, 2023)

Mineral oil detection in ghee using attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR) in conjunction with chemometrics - Kamal Gandhi; Rajan Sharma; Raman Seth; Akshay Ramani; Bimlesh Mann (Food and Humanity, 2023)

Impact of 280 nm UV-C LEDs on the microbial safety and nutritional quality in tender coconut water - Raj Kumar Maguluri; Akshay H. Dasalkar; Siva Sankara Reddy Singam; Sudheer Kumar Yannam (Food and Humanity, 2023)

Validating the credibility of solar simulation tools using a real-world case study - Akshay Kaleshwarwar; Sarika Bahadure (Energy and Buildings, 2023)

Discovery of imidazopyridine-pyrazoline-hybrid structure as SHP-1 agonist that suppresses phospho-STAT3 signaling in human breast cancer cells - Min Hee Yang; Gautam Sethi; Akshay Ravish; Arun Kumar Mohan; Vijay Pandey; Peter E. Lobie; Shreeja Basappa; Basappa Basappa; Kwang Seok Ahn (Chemico-Biological Interactions, 2023)

Physicochemical characteristics of atmospheric particles in south western (Pune) region of India: Elemental size distribution, source analysis and risk assessment - Himanshi Rohra; Akshay Kale; Shashikant Nehul; Atar S. Pipal; Ajay Taneja; P.G. Satsangi (Atmospheric Pollution Research, 2023)

Recent Advances in Nano-metal Oxide-Biochar Composites for Efficient Removal of Environmental Contaminants - Akshay Kumar Dey; Md. Ahmaruzzaman (Reviews of Environmental Contamination and Toxicology, 2023)

Value of process understanding in the era of machine learning: A case for recession flow prediction - Prashant Istalkar; Akshay Kadu; Basudev Biswal (Journal of Hydrology, 2023)

Universal recession constants and their potential to predict recession flow - Durga Sharma; Akshay Kadu; Basudev Biswal (Journal of Hydrology, 2023)

Prediction of ethylene permeance through perforated packaging films using a dimensionless correlation - Akshay D. Sonawane; Jorge C. Oliveira; Cornelia Weltzien; Pramod V. Mahajan (Journal of Food Engineering, 2023)

Genetic diversity, transcript heterogeneity and allele mining of TaSKP1-6B-4 gene variants across diverse genotypes under terminal heat stress and genome wide characterization of TaSKP1 gene family from bread wheat (Triticum aestivum L.) - Praful Jaiswal; Akshay Singh; Kriti Bajpai; Kabitha Tripathi; Anant Narayan Sahi; Sharmistha Barthakur (Plant Molecular Biology, 2023)

Assessment of morpho-cultural, genetic and pathological diversity of Rhizoctonia solani isolates obtained from different host plants - Asmita Singh; Priya Chandra; Amar Bahadur; Prasenjit Debnath; Gopala Krishnan Subbaiyan; Ranjith K. Ellur; Prashantha Siddappa Tadasanahaller; Akshay Kumar Hosahalli Manjunath; Gaurav Kumar Yadav; Bishnu Maya Bashyal (Journal of Plant Pathology, 2023)

Reversal of biological age in multiple rat organs by young porcine plasma fraction - Steve Horvath; Kavita Singh; Ken Raj; Shraddha I. Khairnar; Akshay Sanghavi; Agnivesh Shrivastava; Joseph A. Zoller; Caesar Z. Li; Claudia B. Herenu; Martina Canatelli-Mallat; Marianne Lehmann; Siniša Habazin; et al. (GeroScience, 2023)
Young blood plasma is known to confer beneficial effects on various organs in mice and rats. However, it was not known whether plasma from young adult pigs rejuvenates old rat tissues at the epigenetic level; whether it alters the epigenetic clock, which is a highly accurate molecular biomarker of aging. To address this question, we developed and validated six different epigenetic clocks for rat tissues that are based on DNA methylation values derived from n = 613 tissue samples. As indicated by their respective names, the rat pan-tissue clock can be applied to DNA methylation profiles from all rat tissues, while the rat brain, liver, and blood clocks apply to the corresponding tissue types. We also developed two epigenetic clocks that apply to both human and rat tissues by adding n = 1366 human tissue samples to the training data. We employed these six rat clocks to investigate the rejuvenation effects of a porcine plasma fraction treatment in different rat tissues. The treatment more than halved the epigenetic ages of blood, heart, and liver tissue. A less pronounced, but statistically significant, rejuvenation effect could be observed in the hypothalamus. The treatment was accompanied by progressive improvement in the function of these organs as ascertained through numerous biochemical/physiological biomarkers, behavioral responses encompassing cognitive functions. An immunoglobulin G (IgG) N-glycosylation pattern shift from pro- to anti-inflammatory also indicated reversal of glycan aging. Overall, this study demonstrates that a young porcine plasma-derived treatment markedly reverses aging in rats according to epigenetic clocks, IgG glycans, and other biomarkers of aging.

Influence of injection strategies on ignition patterns of RCCI combustion engine fuelled with hydrogen enriched natural gas - Akshay Loyte; Jiwak Suryawanshi; Girish Bhiogade; Yuvarajan Devarajan; Raja Thandavamoorthy; Ruby Mishra; Natrayan L (Environmental Research, 2023)

Current scenario and challenges in recycling of human urine generated at source in rail coaches as resource - Kashyap Kumar Dubey; Deepanshi Rajput; Anshu Baldia; Akshay Kumar; Vinod Kumar; Ankush Yadav; Shikha Rao; Yogendra Kumar Mishra (Current Opinion in Green and Sustainable Chemistry, 2023)

Multi-heteroatom doped vehicle exhaust soot derived nano-onion based economical and efficient electrodes for microbial fuel cell: A waste to wealth strategy - Yashmeen Budania; Smriti Mishra; Aradhana Mishra; Animesh Jana; Akshay Modi; Ankit Tyagi; Pradip Kumar; Shiv Singh (Chemical Engineering Journal, 2023)

Hyaluronic acid: More than a carrier, having an overpowering extracellular and intracellular impact on cancer - Medha Bhattacharyya; Heena Jariyal; Akshay Srivastava (Carbohydrate Polymers, 2023)

First Report of Exserohilum rostratum Causing Sugarcane Leaf Spot in India - R. Selvakumar; M. Remya; R. B. Akshay Ravi; R. Viswanathan (Sugar Tech, 2023)

Mineral magnetic properties of ultisol profiles from tropical southern India - Mohan Reethu; Kizhur Sandeep; Joju G. Sebastian; Anish K. Warrier; Geetha H. Aravind; Abdul K. Rafaz; Jithin Jose; Radhakrishnan Akshay; Vadakkath V. Suhaiba (Geosciences Journal, 2023)

Salinity and sodicity stresses differentially influence growth and physiology in sapota (Achras zapota L.) - Raj Kumar; Anshuman Singh; Ashwani Kumar; Raj Kumar; Mukesh Kumar Mehla; Akshay Kumar (South African Journal of Botany, 2023)

Assessment of the solar energy potential of diverse urban built forms in Nagpur, India - Akshay Kaleshwarwar; Sarika Bahadure (Sustainable Cities and Society, 2023)

Structural behaviour of steel fibre-reinforced concrete floor system for modular construction - Shan Li; Gilbert Sebastiano Gondokusumo; Akshay Venkateshwaran; J.Y. Richard Liew (Engineering Structures, 2023)

Applications of autotrophic ammonia oxidizers in bio-geochemical cycles - Deepanshi Rajput; Anshu Baldia; Akshay Kumar; Vinod Kumar; Gunda Mohanakrishna; Kashyap Kumar Dubey (Chemical Engineering Journal, 2023)

Spatially activated conserved auxin-transcription factor regulatory module controls de novo root organogenesis in rice - Tushar Garg; Manoj Yadav; Khrang Khrang Khunggur Mushahary; Akshay Kumar; Vivek Pal; Harshita Singh; Mukesh Jain; Shri Ram Yadav (Planta, 2023)

Pharma 4.0: Use of Advanced Multivariate Analytics at Industrial Scale for Process Troubleshooting, Establishing Material Control and Improving Process Robustness in Pharmaceutical Industrial setting: Case Study - Vaidehi Soman; Akshay Hatewar; Adolf Miranda; Abhaykumar Nalawade; Hansraj Gocher; Ram Kumar (Journal of Pharmaceutical Innovation, 2023)

Integrated multiomics analysis of chromosome 19 miRNA cluster in bladder cancer - Akshay Pramod Ware; Kapaettu Satyamoorthy; Bobby Paul (Functional & Integrative Genomics, 2023)
With 46 microRNAs (miRNAs) embedded tandemly over a distance of ~100 kb, chromosome 19 microRNA cluster (C19MC) is the largest miRNA cluster in the human genome. The C19MC is transcribed from a long noncoding genomic region and is usually expressed simultaneously at a higher level. Hence, we performed an integrative multiomics data analysis to examine C19MC regulation, expression patterns, and their impact on bladder cancer (BCa). We found that 43 members of C19MC were highly expressed in BCa. However, its co-localization with recurrent copy number variation (CNV) gain was not statistically significant to implicate its upregulation. It has been reported that C19MC expression is regulated by a well-established CpG island situated 17.6 kb upstream of the transcription start site, but we found that CpG probes at this island were hypomethylated, which was not statistically significant in the BCa cohort. In addition, the promoter region of C19MC is strongly regulated by a group of seven transcription factors ( NR2F6 , SREBF1 , TBP , GATA3 , GABPB1 , ETV4 , and ZNF444 ) and five chromatin modifiers ( SMC3 , KDMA1 , EZH2 , RAD21 , and CHD7 ). Interestingly, these 12 genes were found to be overexpressed in BCa patients. Further, C19MC targeted 42 tumor suppressor (TS) genes that were downregulated, of which 15 were significantly correlated with patient survival. Our findings suggest that transcription factors and chromatin modifiers at the promoter region may regulate C19MC overexpression. The upregulated C19MC members, transcription regulators, and TS genes can be further exploited as potential diagnostic and prognostic indicators as well as for therapeutic management of BCa.

Assessment of air pollution tolerance and anticipated performance index of roadside trees in urban and semi-urban regions - Akshay Kumar Singh; Sushil Kumar Shukla; Pardeep Singh; Sughosh Madhav; Ashutosh Tripathi (Environmental Monitoring and Assessment, 2023)

Evaluation of uranium content and annual ingestion dose in the surface and ground water bodies of Chittorgarh, Rajasthan, India - Tejpal Menaria; Shailesh Nath Tiwari; Akshay Kumar Patra; Inampudi Vijaya Saradhi; A Vinod Kumar; Rama Kanwar Khangarot; Devendra Singh Rathore (Environmental Monitoring and Assessment, 2023)

A Bacteriophage-Loaded Microparticle Laden Topical Gel for the Treatment of Multidrug-Resistant Biofilm-Mediated Burn Wound Infection - Deepa Dehari; Aiswarya Chaudhuri; Dulla Naveen Kumar; Meraj Anjum; Rajesh Kumar; Akshay Kumar; Dinesh Kumar; Gopal Nath; Ashish Kumar Agrawal (AAPS PharmSciTech, 2023)

Chromatography-mass spectrometry based chemical profiling of Mucuna pruriens (L.) DC. and its beneficial effect against hydrogen peroxide-induced oxidative stress in HEK 293T cells and breast cancer cells - D. Sruthi; Anagha Jagannathan; Akshay B. Chandran; H.C.Yashavantha Rao; C. Jayabaskaran (South African Journal of Botany, 2023)

A novel strategy to design lattice structures with zero Poisson’s ratio - Bikram Jyoti Sahariah; Manash Jyoti Baishya; Akshay Namdeo; Prasenjit Khanikar (Engineering Structures, 2023)

A comprehensive record of the fishery resources of a tropical Ramsar wetland: Ashtamudi Estuary, India - Akshay .A. Kumar; Anvar Ali P. H.; Sreekanth Giri Bhavan (Marine Biodiversity, 2023)

Mineralogical variations and geochemical distribution of rare earths and Yttrium (REY) in coal and overburden rocks of some Indian coal mines of Gondwana coalfield - Santosh Kumar; Akshay K Singh Choudhary; A Keshav Krishna; Sudip Maity (Journal of Earth System Science, 2023)

Predictive analysis for pathogenicity classification of H5Nx avian influenza strains using machine learning techniques - Akshay Chadha; Rozita Dara; David L. Pearl; Shayan Sharif; Zvonimir Poljak (Preventive Veterinary Medicine, 2023)

Exome sequencing of choreoacanthocytosis reveals novel mutations in VPS13A and co-mutation in modifier gene(s) - Sima Chaudhari; Akshay Pramod Ware; Dushyanth Babu Jasti; Sankar Prasad Gorthi; Lavanya Prakash Acharya; Manoj Bhat; Sandeep Mallya; Kapaettu Satyamoorthy (Molecular Genetics and Genomics, 2023)
Choreoacanthocytosis, one of the forms of neuroacanthocytosis, is caused by mutations in vacuolar protein sorting-associated protein A ( VPS13A ), and is often misdiagnosed with other form of neuroacanthocytosis with discrete genetic defects. The phenotypic variations among the patients with VPS13A mutations significantly obfuscates the understanding of the disease and treatment strategies. In this study, two unrelated cases were identified, exhibiting the core phenotype of neuroacanthocytosis but with considerable clinical heterogeneity. Case 1 presented with an additional Parkinsonism phenotype, whereas seizures were evident in case 2. To decipher the genetic basis, whole exome sequencing followed by validation with Sanger sequencing was performed. A known homozygous pathogenic nonsense mutation (c.799C > T; p.R267X) in exon 11 of the VPS13A gene was identified in case 1 that resulted in a truncated protein. A novel missense mutation (c.9263T > G; p.M3088R) in exon 69 of VPS13A identified in case 2 was predicted as pathogenic. In silico analysis of the p.M3088R mutation at the C-terminus of VPS13A suggests a loss of interaction with TOMM40 and may disrupt mitochondrial localization. We also observed an increase in mitochondrial DNA copy numbers in case 2. Mutation analysis revealed benign heterozygous variants in interacting partners of VPS13A such as VAPA in case 1. Our study confirmed the cases as ChAc and identified the novel homozygous variant of VPS13A (c.9263T > G; p.M3088R) within the mutation spectrum of VPS13A- associated ChAc. Furthermore, mutations in VPS13A and co-mutations in its potential interacting partner(s) might contribute to the diverse clinical manifestations of ChAc, which requires further study.

Correction to: Repurposing of artesunate, an antimalarial drug, as a potential inhibitor of hepatitis E virus - Neha Bhise; Megha Agarwal; Nidhi Thakur; P. S. Akshay; Sarah Cherian; Kavita Lole (Archives of Virology, 2023)

Environmental impacts of air pollution and its abatement by plant species: A comprehensive review - Akshay Kumar Singh; Manoj Kumar; Kuldeep Bauddh; Ajai Singh; Pardeep Singh; Sughosh Madhav; Sushil Kumar Shukla (Environmental Science and Pollution Research, 2023)

A physical tug-of-war and the evolution of immune cells - Akshay Tiwari; Narendra M Dixit (Journal of Biosciences, 2023)

Cucumber F1 hybrid derived from two contrasting inbreds ensures high frequency gynogenesis for induction of haploids through a modified in vitro based protocol - N. Pradeepkumara; S.S. Dey; A.D. Munshi; T.K. Behera; Reeta Bhatia; Khushboo Kumari; Pragya Prakash; R.C. Bhattacharya; Akshay Talukdar (South African Journal of Botany, 2023)

Carbon black and chitin nanofibers for green tyres: Preparation and property evaluation - Mariya Mathew; C.D. Midhun Dominic; K.V. Neenu; P.M. Sabura Begum; P. Dileep; T.G. Ajith Kumar; Akshay Alax Sabu; Dhiraj Nagane; Jyotishkumar Parameswaranpillai; Michael Badawi (Carbohydrate Polymers, 2023)

Methyl orange dye adsorption and degradation at low temperature using iron oxide-incorporated biochar derived from industrial by-products - Ranjana Ramath; Akshay Madappilly Sukumaran; Anjana Ramachandran; Sajeena Beevi Basheer (Bioresource Technology Reports, 2023)

Using passive acoustic monitoring to examine the impacts of ecological restoration on faunal biodiversity in the Western Ghats - Vijay Ramesh; Priyanka Hariharan; V.A. Akshay; Pooja Choksi; Sarika Khanwilkar; Ruth DeFries; V.V. Robin (Biological Conservation, 2023)

CADNet: an advanced architecture for automatic detection of coronary artery calcification and shadow border in intravascular ultrasound (IVUS) images - Priyanka Arora; Parminder Singh; Akshay Girdhar; Rajesh Vijayvergiya; Prince Chaudhary (Physical and Engineering Sciences in Medicine, 2023)

A comparative analysis of the vertical accuracy of multiple open-source digital elevation models for the mountainous terrain of the north-western Himalaya - Parvaiz Ahmad Ganie; Ravindra Posti; Akshay Singh Aswal; Vidya Shree Bharti; Vinay Kumar Sehgal; Debajit Sarma; Pramod Kumar Pandey (Modeling Earth Systems and Environment, 2023)

Erythrocyte miRNA-92a-3p interactions with PfEMP1 as determinants of clinical malaria - Sowmya R. Prabhu; Akshay Pramod Ware; Shashikiran Umakanth; Manjunath Hande; Chakrapani Mahabala; Abdul Vahab Saadi; Kapaettu Satyamoorthy (Functional & Integrative Genomics, 2023)
Based on the recently added high throughput analysis data on small noncoding RNAs in modulating disease pathophysiology of malaria, we performed an integrative computational analysis for exploring the role of human-host erythrocytic microRNAs (miRNAs) and their influence on parasite survival and host homeostasis. An in silico analysis was performed on transcriptomic datasets accessed from PlasmoDB and Gene Expression Omnibus (GEO) repositories analyzed using miRanda, miRTarBase, mirDIP, and miRDB to identify the candidate miRNAs that were further subjected to network analysis using MCODE and DAVID. This was followed by immune infiltration analysis and screening for RNA degradation mechanisms. Seven erythrocytic miRNAs, miR-451a, miR-92a-3p, miR-16-5p, miR-142-3p, miR-15b-5p, miR-19b-3p, and miR-223-3p showed favourable interactions with parasite genes expressed during blood stage infection. The miR-92a-3p that targeted the virulence gene PfEMP1 showed drastic reduction during infection. Performing pathway analysis for the human-host gene targets for the miRNA identified TOB1 , TOB2 , CNOT4 , and XRN1 genes that are associated to RNA degradation processes, with the exoribonuclease XRN1 , highly enriched in the malarial samples. On evaluating the role of exoribonucleases in miRNA degradation further, the pattern of Plasmodium falciparum _XRN1 showed increased levels during infection thus suggesting a defensive role for parasite survival. This study identifies miR-92a-3p, a member of C13orf25/ miR-17-92 cluster, as a novel miRNA inhibitor of the crucial parasite genes responsible for symptomatic malaria. Evidence for a plausible link to chromosome 13q31.3 loci controlling the epigenetic disease regulation is also suggested.

Brief status of contamination in surface water of rivers of India by heavy metals: a review with pollution indices and health risk assessment - Akshay Botle; Sayli Salgaonkar; Rahul Tiwari; Shushama Ambadekar; Gayatri R. Barabde (Environmental Geochemistry and Health, 2023)

Dynamic behaviour of integral abutment bridge transition under moving train loads - Akshay Sakhare; Piyush Punetha; Naveen Kumar Meena; Sanjay Nimbalkar; G.-R. Dodagoudar (Transportation Geotechnics, 2023)

Fish assemblage and guild structure in the Ashtamudi Estuary, a tropical Ramsar site in India - Akshay .A. Kumar; Anvar Ali PH; Giri Bhavan Sreekanth (Journal of Environmental Management, 2023)

Application of hybrid Taguchi L16 and desirability for model prediction and optimization in assessment of the performance of a novel Water Hyacinth biodiesel run diesel engine - Akshay Jain; Bhaskor Jyoti Bora; Rakesh Kumar; Prabhakar Sharma; Balakrishnan Deepanraj; Kashif Irshad; Ch. Ravikiran (Fuel, 2023)

Impact of spatial distribution on the sensory properties of multiphase 3D-printed food configurations - Johannes Burkard; Akshay Nain Shah; Eugenia Harms; Christoph Denkel (Food Quality and Preference, 2023)

Food processing applications of protease activity identified in the methotrexate degrading enzyme of Variovorax paradoxus - Kulkarni Akshay Narayanrao; Venkata Krishna Bayineni; Chandan Kumar Sahu; Ravi-Kumar Kadeppagari (Food and Bioproducts Processing, 2023)

Repurposing of artesunate, an antimalarial drug, as a potential inhibitor of hepatitis E virus - Neha Bhise; Megha Agarwal; Nidhi Thakur; P. S. Akshay; Sarah Cherian; Kavita Lole (Archives of Virology, 2023)

Correction to: Development and evaluation of sunscreen cream containing solid lipid nanoparticles of Spinacia oleraceae - Vijisha Taniyadukkam; Jobin Jose; Naseer Maliyakkal; Asmy Appadath Beeran; Muhammad Ali Abdullah Almoyad; Lotfi Aleya; Akshay Bandiwadekar (Environmental Science and Pollution Research, 2023)

Upcycling of spent granular carbon into sustainable and recyclable biopolymeric hybrid hydrogel for highly efficient adsorptive removal of tetracycline pollutant from environmental waters and industrial effluents - Pooja V. Devre; Akshay S. Patil; Daewon Sohn; Anil H. Gore (Journal of Environmental Chemical Engineering, 2023)

Genetic mapping of some key plant architecture traits in Brassica juncea using a doubled haploid population derived from a cross between two distinct lines: vegetable type Tumida and oleiferous Varuna - Shikha Mathur; Priyansha Singh; Satish Kumar Yadava; Vibha Gupta; Akshay Kumar Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2023)

Foliar zinc fertilization improves yield, biofortification and nutrient-use efficiency of upland rice - Akshay Kumar Yogi; Ram Swaroop Bana; Shanti D. Bamboriya; Ram L. Choudhary; Alison M. Laing; Deepak Singh; Samarth Godara; Subhash Babu; Amresh Chaudhary (Nutrient Cycling in Agroecosystems, 2023)

A State-Of-The-Art Review on Coronary Artery Border Segmentation Algorithms for Intravascular Ultrasound (IVUS) Images - Priyanka Arora; Parminder Singh; Akshay Girdhar; Rajesh Vijayvergiya (Cardiovascular Engineering and Technology, 2023)

Differential expression of outer membrane proteins and quinolone resistance determining region mutations can lead to ciprofloxacin resistance in Salmonella Typhi - Sadanand Dangari Akshay; Srajana Nayak; Vijaya Kumar Deekshit; Anusha Rohit; Biswajit Maiti (Archives of Microbiology, 2023)

Molecular phylogeny and genetic diversity of some Lepidagathis species (Acanthaceae) based on nuclear and chloroplast regions - Suhas K. Kadam; Asif S. Tamboli; Rohit N. Mane; Akshay P. Jangam; Shrirang R. Yadav; Yeon-Sik Choo; Jae Hong Pak (Plant Biosystems, 2023)

Solar light–based advanced oxidation processes for degradation of methylene blue dye using novel Zn-modified CeO2@biochar - Akshay Kumar Dey; Soumya Ranjan Mishra; Md. Ahmaruzzaman (Environmental Science and Pollution Research, 2023)

Genetic engineering of plants for phytoremediation: advances and challenges - Kundan Kumar; Akshay Shinde; Varad Aeron; Aanchal Verma; Naseera Sayed Arif (Journal of Plant Biochemistry and Biotechnology, 2023)

Design of a supervisory control system for autonomous operation of advanced reactors - Akshay J. Dave; Taeseung Lee; Roberto Ponciroli; Richard B. Vilim (Annals of Nuclear Energy, 2023)

Development and evaluation of sunscreen cream containing solid lipid nanoparticles of Spinacia oleraceae - Vijisha Taniyadukkam; Jobin Jose; Naseer Maliyakkal; Asmy Appadath Beeran; Muhammad Ali Abdullah Almoyad; Lotfi Aleya; Akshay Bandiwadekar (Environmental Science and Pollution Research, 2023)

Transcription factors controlling the expression of oxidative stress associated genes in rice (Oryza sativa L.) - D. Sujitha; H. G. Jalendra Kumar; Garima Thapliayal; Garima Pal; P. A. Vanitha; Akshay Uttarkar; Mahesh Patil; B. H. Rajashekar Reddy; Vidya Niranjan; Usha Rayalcheruvu; Geetha Govind; M. Udayakumar; et al. (Plant Biotechnology Reports, 2023)

Development of an improved solids-liquid separation reactor for floatable & settleable solids in DAF slurry of a slaughterhouse - Akshay D. Shende; N.N. Rao; Girish R. Pophali (Journal of Water Process Engineering, 2023)

Urinary tract infection and sepsis causing potential of multidrug-resistant Extraintestinal pathogenic E. coli isolated from plant-origin foods - Priyanka Priyanka; Prem Raj Meena; Dharma Raj; Anuj Rana; Akshay Dhanokar; K Siddaardha Duggirala; Arvind Pratap Singh (International Journal of Food Microbiology, 2023)

Groundwater potential zone demarcation in the Khadir Island of Kachchh, Western India - Avinash Goswami; Naresh Gor; Akshay Jyoti Borah; Gaurav Chauhan; Dipankar Saha; Girish Ch. Kothyari; Dimpi Barpatra; Amborish Hazarika; Abhishek Lakhote; Chirag Jani; Jaymeet Solanki; M.G. Thakkar (Groundwater for Sustainable Development, 2023)

Multiomics and optobiotechnological approaches for the development of microalgal strain for production of aviation biofuel and biorefinery - Akshay Kumar; Anshu Baldia; Deepanshi Rajput; Suneel Kateriya; Vikash Babu; Kashyap Kumar Dubey (Bioresource Technology, 2023)

Spatial connections in extreme precipitation events obtained from NWP forecasts: A complex network approach - Akshay Singhal; Muhammed Jaseem; Sanjeev K. Jha (Atmospheric Research, 2023)

Performance of the Indian summer monsoon 2020 in NCEP-GFS - Pemmani Venkata Subba Raju; Akshay Kulkarni; Muhammed Muhshif Karadan; Dongxiao Wang (Acta Geophysica, 2023)

Prediction of meteorological drought and standardized precipitation index based on the random forest (RF), random tree (RT), and Gaussian process regression (GPR) models - Ahmed Elbeltagi; Chaitanya B. Pande; Manish Kumar; Abebe Debele Tolche; Sudhir Kumar Singh; Akshay Kumar; Dinesh Kumar Vishwakarma (Environmental Science and Pollution Research, 2023)

Relating forecast and satellite precipitation to generate future skillful ensemble forecasts over the northwest Himalayas at major avalanche and glacier sites - Akshay Singhal; Athul Cheriyamparambil; Nibedita Samal; Sanjeev K. Jha (Journal of Hydrology, 2023)

Engineering microalgae as the next-generation food - Anshu Baldia; Deepanshi Rajput; Akshay Kumar; Ashok Pandey; Kashyap Kumar Dubey (Systems Microbiology and Biomanufacturing, 2023)

A Novel Change Point Detection Approach for Analysis of Time-Ordered Satellite Imagery - Ashwin Yadav; Kamal Jain; Akshay Pandey; Joydeep Majumdar (Journal of the Indian Society of Remote Sensing, 2023)

Evolution of Bcl-2 Anthogenes (BAG) as the Regulators of Cell Death in Wild and Cultivated Oryza Species - Ruchi Bansal; Surbhi Kumawat; Pallavi Dhiman; Sreeja Sudhakaran; Nitika Rana; Rajdeep Jaswal; Akshay Singh; Humira Sonah; Tilak Raj Sharma; Rupesh Deshmukh (Journal of Plant Growth Regulation, 2023)

Ontogenetic Dietary Shift in Megabenthic Predatory Elasmobranchs of a Tropical Estuarine Bay - Deepa Shashikant Yogi; Akshay Naik; Prema Piyusha Panda; Ranjana Yadav; Aniket Desai; Mandar Nanajkar (Estuaries and Coasts, 2023)

Actinomyces ruminis sp. nov., an obligately anaerobic bacterium isolated from the rumen of cattle - Vikram B. Lanjekar; Sai Suresh Hivarkar; Gowdaman Vasudevan; Akshay Joshi; Prashant K. Dhakephalkar; Sumit Singh Dagar (Archives of Microbiology, 2023)

Chemical characterization, thrombolytic and antioxidant activity of Hibiscus tiliaceus L. leaves - Ajaykumar Rikhabchand Surana; Manoj Ramesh Kumbhare; Akshay Rambhau Gunjal; Sonam Shambhupuri Goswami; Dipali Manik Ghuge (Natural Product Research, 2022)

A Model Combination Approach for Improving Streamflow Prediction - Akshay Kadu; Basudev Biswal (Water Resources Management, 2022)

Year-round sustainable biomass production potential of Nannochloris sp. in outdoor raceway pond enabled through strategic photobiological screening - Kenny Paul; Mahadev Gaikwad; Poonam Choudhary; Natarajan Mohan; Puja Pai; Smita D. Patil; Yogesh Pawar; Akshay Chawande; Arun Banerjee; Vinod Nagle; Meenakshi Chelliah; Ajit Sapre; et al. (Photosynthesis Research, 2022)

CmirC: an integrated database of clustered miRNAs co-localized with copy number variations in cancer - Akshay Pramod Ware; Kapaettu Satyamoorthy; Bobby Paul (Functional & Integrative Genomics, 2022)
Genomic rearrangements and copy number variations (CNVs) are the major regulators of clustered microRNAs (miRNAs) expression. Several clustered miRNAs are harbored in and around chromosome fragile sites (CFSs) and cancer-associated genomic hotspots. Aberrant expression of such clusters can lead to oncogenic or tumor suppressor activities. Here, we developed CmirC ( C lustered miR NAs co-localized with C NVs), a comprehensive database of clustered miRNAs co-localized with CNV regions. The database consists of 481 clustered miRNAs co-localized with CNVs and their expression patterns in 35 cancer types of the TCGA. The portal also provides information on CFSs, miRNA cluster candidates, genomic coordinates, target gene networks, and gene functionality. The web portal is integrated with advanced tools such as JBrowse, NCBI-BLAST, GeneSCF, visNetwork, and NetworkD3 to help the researchers in data analysis, visualization, and browsing. This portal provides a promising avenue for integrated data analytics and offers additional evidence for the complex regulation of clustered miRNAs in cancer. The web portal is freely accessible at http://slsdb.manipal.edu/cmirclust to explore clinically significant miRNAs.

Divulging the anti-acetylcholinesterase activity of Colletotrichum lentis strain KU1 extract as sustainable AChE active site inhibitors - Anoop Kallingal; Aravind Ayyolath; Varun Thachan Kundil; Akshay Maniyeri Suresh; Tomy Muringayil Joseph; Józef Haponiuk; Sabu Thomas; Anu Augustine (Archives of Microbiology, 2022)

Analysis of deficit summer monsoon rainfall over India in CMIP5 simulations - Akshay Kulkarni; Ashwini Kulkarni; S S Sabade; P V S Raju (Journal of Earth System Science, 2022)

Effect of sub-minimum inhibitory concentration of ceftriaxone on the expression of outer membrane proteins in Salmonella enterica serovar Typhi - Sadanand Dangari Akshay; Karanth Padyana Anupama; Vijaya Kumar Deekshit; Anusha Rohit; Biswajit Maiti (World Journal of Microbiology and Biotechnology, 2022)

pH-Dependent supersaturation from amorphous solid dispersions of weakly basic drugs - Bo Wang; Matthew J. Nethercott; Akshay Narula; Michael Hanrahan; Shanming Kuang; Robert M. Wenslow; Na Li (Pharmaceutical Research, 2022)

Effect of association of temperature and pollutant levels on COVID-19 spread over Jaipur - P. Chaitanya; Era Upadhyay; Akshay Kulkarni; P. V. S. Raju (Vegetos, 2022)

Effect of size variation of fibre-shaped waste tyre rubber as fine aggregate on the ductility of self-compacting concrete - Akshay Anil Thakare; Amardeep Singh; Trilok Gupta; Sandeep Chaudhary (Environmental Science and Pollution Research, 2022)

Correction to: Spatio-temporal variability and trend analysis of rainfall in Wainganga river basin, Central India, and forecasting using state-space models - Nanabhau S. Kudnar; Pranaya Diwate; Varun Narayan Mishra; Prashant K. Srivastava; Akshay Kumar; Manish Pandey (Theoretical and Applied Climatology, 2022)

Spatio-temporal variability and trend analysis of rainfall in Wainganga river basin, Central India, and forecasting using state-space models - Nanabhau S. Kudnar; Pranaya Diwate; Varun Narayan Mishra; Prashant K. Srivastava; Akshay Kumar; Manish Pandey (Theoretical and Applied Climatology, 2022)

Toxicity, Environmental Monitoring and Removal Strategies of Arsenic - Akshay Pawar; Simranjeet Singh; Praveen Chandra Ramamurthy; Amith G. Anil; Nabila Shehata; Daljeet Singh Dhanjal; Tandreborekaval Swamy Sunil Kumar Naik; Parul Parihar; Ram Prasad; Joginder Singh (International Journal of Environmental Research, 2022)

Assessment of groundwater quality and human health risks from fluoride in Lower Satluj Basin, Punjab, India - Akshay Kumar Chaudhry; Payal Sachdeva (Arabian Journal of Geosciences, 2022)

Diversity and spatial distribution of butterflies in different macrohabitat of North East India - Prasun Karmakar; Akshay Mishra; Chandan Borah; Arabinda Deka (International Journal of Tropical Insect Science, 2022)

A systematic basin-wide approach for locating and assessing volumetric potential of rainwater harvesting sites in the urban area - Deshbhushan Patil; Gaurav Kumar; Akshay Kumar; Rajiv Gupta (Environmental Science and Pollution Research, 2022)

Characterization of Cry2 genes (CRY2a and CRY2b) of B. napus and comparative analysis of BnCRY1 and BnCRY2a in regulating seedling photomorphogenesis - Pooja Sharma; Sushma Mishra; Naini Burman; Mithu Chatterjee; Shipra Singh; Akshay K. Pradhan; Paramjit Khurana; Jitendra P. Khurana (Plant Molecular Biology, 2022)

Glyphosate-resistant Brassica juncea (oilseed mustard) transgenics for possible control of root parasite Orobanche aegyptiaca and conservation agriculture - Parul Agarwal; Arundhati Mukhopadhyay; Vibha Gupta; Akshay Kumar Pradhan; Deepak Pental (Journal of Plant Biochemistry and Biotechnology, 2022)

A review on mineralogical speciation, global occurrence and distribution of rare earths and Yttrium (REY) in coal ash - Akshay K Singh Choudhary; Santosh Kumar; Sudip Maity (Journal of Earth System Science, 2022)

The influence of strip load on the seismic design of cantilever sheet pile walls: a simplified analytical solution - Akshay Pratap Singh; Kaustav Chatterjee (Bulletin of Earthquake Engineering, 2022)

Assessment of Role and Efficacy of Curcumin and Quercetin in Preventing Lead-Induced Oxidative Stress in Rats - Mohd Zahid; Pushkar Singh Rawat; Shalini Singh; Akshay Kumar Gupta; Rumana Ahmad; Abbas Ali Mahdi; Md. Kaleem Ahmad; Sudhir Mehrotra (Indian Journal of Clinical Biochemistry, 2022)

An accelerated carbonation and its effect on concrete containing natural zeolite - Akshay Ramesh Bura; B. Kondraivendhan (Innovative Infrastructure Solutions, 2022)

Association mapping, trait variation, interaction and population structure analysis in cucumber (Cucumis sativus L.) - Rahul Kumar; Anilabh Das Munshi; Tusar Kanti Behera; Gograj Singh Jat; Harshawardhan Choudhary; Akshay Talukdar; Prasanta Dash; Deepak Singh (Genetic Resources and Crop Evolution, 2022)

Moringa oleifera-derived coagulants for water treatment: Floc structure, residual organics, and performance trade-offs - Akshay Murali; Kyle D. Hillstead; Brendan S. Wrobel; Daniel J. Thomas; Romuald Gonety; Volodymyr V. Tarabara (Environmental Science and Pollution Research, 2022)

An application of multiple‐point statistics downscaling approach over North‐West Himalayas in avalanche‐prone areas - Akshay Singhal; Sanjeev K. Jha (International Journal of Climatology, 2022)
Weather data at fine spatial resolution in the Himalayan region are important for assessing various hydrological events such as avalanches. In recent years, national agencies have been exploring the use of Weather Research and Forecasting (WRF) model in this region. Setting up a WRF model with fine spatial grids in the Himalayan region is challenging due to large topographical variations and associated computational cost. In this study, we use High Asia Refined analysis (HAR) dataset to set up a Multiple‐Point Statistics (MPS) based downscaling approach using the hindcast data of years 2001–2012 at both coarse and fine spatial grids. A total of 11 covariates are used in the study belonging to various environmental factors such as weather, location, topography and vegetation. We generate multiple realizations of precipitation and temperature for the year 2013. The efficacy of the MPS model is tested in a gridbox consisting of 61 × 61 grids, in 10 districts and at sites prone to avalanches and extreme precipitation events. Results show that the downscaled precipitation and temperature have reasonable accuracy. Mean monthly root mean square error and mean absolute error values for precipitation range between 2.87–8.0 mm and 1.45–3.27 mm, respectively. For temperature, both the error statistics range between 0.65–1.13 K and 0.51–0.83 K, respectively. Overall, the study shows that MPS is an effective tool for generating reliable fine‐resolution weather information over multiple geographical locations, overcoming the diverse challenges of the Northwest Himalayas. Furthermore, it is capable of providing consistent fine‐resolution weather data at point locations. Such data may be highly sensitive for hydrological studies, such as avalanche forecasting in the Himalayas.

Fluorescence-Based Detection of Cholesterol Using Inclusion Complex of Hydroxypropyl-β-Cyclodextrin and l-Tryptophan as the Fluorescence Probe - Akshay Holkar; Sharwari Ghodke; Prachi Bangde; Prajakta Dandekar; Ratnesh Jain (Journal of Pharmaceutical Innovation, 2022)

Emerging Novel Approaches for the Enhanced Delivery of Natural Products for the Management of Neurodegenerative Diseases - Akshay Bandiwadekar; Jobin Jose; Maryam Khayatkashani; Solomon Habtemariam; Hamid Reza Khayat Kashani; Seyed Mohammad Nabavi (Journal of Molecular Neuroscience, 2022)

Botanicals for Sustainable Management of Stored Food Grains: Pesticidal Efficacy, Mode of Action and Ecological Risk Assessment Using Computational Approaches - Bhanu Prakash; Prem Pratap Singh; Akshay Kumar; Vishal Gupta (Anthropocene Science, 2022)

Air pollution perception in ten countries during the COVID-19 pandemic - Baowen Lou; Diego Maria Barbieri; Marco Passavanti; Cang Hui; Akshay Gupta; Inge Hoff; Daniela Antunes Lessa; Gaurav Sikka; Kevin Chang; Kevin Fang; Louisa Lam; Brij Maharaj; et al. (Ambio, 2022)
As largely documented in the literature, the stark restrictions enforced worldwide in 2020 to curb the COVID-19 pandemic also curtailed the production of air pollutants to some extent. This study investigates the perception of the air pollution as assessed by individuals located in ten countries: Australia, Brazil, China, Ghana, India, Iran, Italy, Norway, South Africa and the USA. The perceptions towards air quality were evaluated by employing an online survey administered in May 2020. Participants ( N = 9394) in the ten countries expressed their opinions according to a Likert-scale response. A reduction in pollutant concentration was clearly perceived, albeit to a different extent, by all populations. The survey participants located in India and Italy perceived the largest drop in the air pollution concentration; conversely, the smallest variation was perceived among Chinese and Norwegian respondents. Among all the demographic indicators considered, only gender proved to be statistically significant.

Priority ranking of road pavements for maintenance using analytical hierarchy process and VIKOR method - Vineesha Chundi; Sridhar Raju; Akshay Ravindra Waim; Subhransu Sekhar Swain (Innovative Infrastructure Solutions, 2022)

Population structure, gene flow and genetic diversity analyses based on agro-morphological traits and microsatellite markers within cultivated and wild germplasms of okra [Abelmoschus esculentus (L.) Moench.] - Anjan Das; Ramesh Kumar Yadav; Harshwardhan Choudhary; Suman Lata; Saurabh Singh; Chavlesh Kumar; Shilpi Kumari; G. Boopalakrishnan; Rakesh Bhardwaj; Akshay Talukdar (Genetic Resources and Crop Evolution, 2022)

Seed longevity studies in wild type, cultivated and inter-specific recombinant inbred lines (RILs) of soybean [Glycine max (L.) Merr.] - Subhash Chandra; Akshay Talukdar; Yashpal Taak; Raju R. Yadav; Manisha Saini; N. S. Sipani (Genetic Resources and Crop Evolution, 2022)

Quercetin Mitigates Red Blood Cell Membrane Bound Na+, K+-ATPase Transporter During Human Aging - Akshay Kumar; Pawan Kumar Maurya (The Journal of Membrane Biology, 2021)

Monsoonal rainfall induced shallow earthquake Swarm in the Amravati district of the central India - Monika Wadhawan; Naresh Rana; Vineet Gahalaut; Manjeet Singh; Kulbir Singh; G Suresh; O P Mishra; Akshay Kumar Joshi; A V Kulkarni; Mahendra Singh; A K Das (Journal of Earth System Science, 2021)

Modeling future irrigation water demands in the context of climate change: a case study of Jayakwadi command area, India - Akshay Sunil; B. Deepthi; A. B. Mirajkar; S. Adarsh (Modeling Earth Systems and Environment, 2021)

Infected insect gut reveals differentially expressed proteins for cellular redox, metal resistance and secretion system in Yersinia enterocolitica-Helicoverpa armigera pathogenic model - Shruti Ahlawat; Amarjeet Kumar Singh; Akshay Shankar; Asha Yadav; Krishna Kant Sharma (Biotechnology Letters, 2021)

Modeling and simulation study to identify threonine synthase as possible drug target in Leishmania major - Rohan J. Meshram; Kamini T. Bagul; Snehal U. Aouti; Akshay M. Shirsath; Harleen Duggal; Rajesh N. Gacche (Molecular Diversity, 2021)

Electrochemical Probing of H2O2 Using TiO2-ZrO2-HfO2 Modified Glassy Carbon Electrode: A Promoted Sacrificial Behavior of Hf4+ ions - Akshay Krishnakumar; Parthasarathy Srinivasan; Ganesh Kumar Mani; Rio Kita; Kunio Okimura; John Bosco Balaguru Rayappan; Kazuyoshi Tsuchiya (Water, Air, & Soil Pollution, 2021)

Assessment of WRF-CHEM Simulated Dust Using Reanalysis, Satellite Data and Ground-Based Observations - Akshay Rajeev; Charu Singh; Sanjeev Kumar Singh; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2021)

Disruptions in oral and nasal microbiota in biomass and tobacco smoke associated chronic obstructive pulmonary disease - Dhiraj M. Agarwal; Dhiraj P. Dhotre; Shreyas V. Kumbhare; Akshay H. Gaike; Bill B. Brashier; Yogesh S. Shouche; Sanjay K. Juvekar; Sundeep S. Salvi (Archives of Microbiology, 2021)

Acid resistance of fine bone china ceramic aggregate concrete - Salman Siddique; Trilok Gupta; Akshay Anil Thakare; Vivek Gupta; Sandeep Chaudhary (European Journal of Environmental and Civil Engineering, 2021)

Fusarium head blight of wheat in India‐variability in pathogens associated and sources of resistance: an overview - Mahender Singh Saharan; H. M. Akshay Kumar; Malkhan Singh Gurjar; Rashmi Aggarwal (Indian Phytopathology, 2021)

Statistical interpretation of environmental influencing parameters on COVID-19 during the lockdown in Delhi, India - Amit Awasthi; Aditi Sharma; Prabhjot Kaur; Balakrishnaiah Gugamsetty; Akshay Kumar (Environment, Development and Sustainability, 2021)

Optimal selection of “zero liquid discharge” (ZLD) system using “analytical hierarchy process” (AHP) and “grey relational analysis” (GRA) - Akshay D. Shende; Asha B. Chelani; N. N. Rao; Girish R. Pophali (Environment, Development and Sustainability, 2021)

Groundwater quality assessment using geospatial technique based water quality index (WQI) approach in a coal mining region of India - Akshay Kumar; Akhouri Pramod Krishna (Arabian Journal of Geosciences, 2021)

Tailored Doxycycline Hyclate Loaded In Situ Gel for the Treatment of Periodontitis: Optimization, In Vitro Characterization, and Antimicrobial Studies - Ketan M. Ranch; Furqan A. Maulvi; Akshay R. Koli; Ditixa T. Desai; Rajesh K. Parikh; Dinesh O. Shah (AAPS PharmSciTech, 2021)

EEG-based hybrid QWERTY mental speller with high information transfer rate - Er. Akshay Katyal; Rajesh Singla (Medical & Biological Engineering & Computing, 2021)

Calibration of Satellite Imagery with Multispectral UAV Imagery - Kamal Jain; Akshay Pandey (Journal of the Indian Society of Remote Sensing, 2021)

Influence of compressive load on concrete filled steel tubular column with variable thickness - Dhiraj Ahiwale; Rushikesh Khartode; Akshay Bhapkar; Giridhar Narule; Kamalkishor Sharma (Innovative Infrastructure Solutions, 2021)

Determination of sensitivity of drainage morphometry towards hydrological response interactions for various datasets - Akshay Omprakash Jain; Tejaskumar Prakashchandra Thaker; Anil Kumar Misra; Anupam Kumar Singh; Priyanka Kumari (Environment, Development and Sustainability, 2021)

Albumin-Mediated Uptake Improves Human Clearance Prediction for Hepatic Uptake Transporter Substrates Aiding a Mechanistic In Vitro-In Vivo Extrapolation (IVIVE) Strategy in Discovery Research - Na Li; Akshay Badrinarayanan; Kazuya Ishida; Xingwen Li; John Roberts; Shuai Wang; Mike Hayashi; Anshul Gupta (The AAPS Journal, 2021)

Damage Characteristics of Jalore Granitic Rocks After Thermal Cycling Effect for Nuclear Waste Repository - P. K. Gautam; R. Dwivedi; Akshay Kumar; Anil Kumar; A. K. Verma; K. H. Singh; T. N. Singh (Rock Mechanics and Rock Engineering, 2021)

Anaerobic treatment of slaughterhouse wastewater: a review - Akshay D. Shende; Girish R. Pophali (Environmental Science and Pollution Research, 2021)

Correction to: Reflections on designing population surveys for COVID-19 infection and prevalence - Akshay Swaminathan; S. V. Subramanian (GeroScience, 2020)

Reflections on designing population surveys for COVID-19 infection and prevalence - Akshay Swaminathan; S. V. Subramanian (GeroScience, 2020)

Dendritic morphology and inhibitory regulation distinguish dentate semilunar granule cells from granule cells through distinct stages of postnatal development - Akshay Gupta; Archana Proddutur; Yun-Juan Chang; Vidhatri Raturi; Jenieve Guevarra; Yash Shah; Fatima S. Elgammal; Vijayalakshmi Santhakumar (Brain Structure and Function, 2020)

Genetics and mapping of seed coat impermeability in soybean using inter-specific populations - Subhash Chandra; Yashpal Taak; Darasing Ramsing Rathod; Raju Ratan Yadav; Shatakshi Poonia; V. Sreenivasa; Akshay Talukdar (Physiology and Molecular Biology of Plants, 2020)

Elucidation of antifungal toxicity of Callistemon lanceolatus essential oil encapsulated in chitosan nanogel against Aspergillus flavus using biochemical and in-silico approaches - Prem Pratap Singh; Akshay Kumar; Bhanu Prakash (Food Additives & Contaminants: Part A, 2020)

Segmental Variations in the Peel Characteristics of the Porcine Thoracic Aorta - Manoj Myneni; Akshay Rao; Mingliang Jiang; Michael R. Moreno; K. R. Rajagopal; Chandler C. Benjamin (Annals of Biomedical Engineering, 2020)

Influence of soil type on static response of cantilever sheet pile walls under surcharge loading: a numerical study - Akshay Pratap Singh; Kaustav Chatterjee (Arabian Journal of Geosciences, 2020)

Advancements in Cancer Stem Cell Isolation and Characterization - Heena Jariyal; Chanchal Gupta; Vedika Sandeep Bhat; Jayant Ramakant Wagh; Akshay Srivastava (Stem Cell Reviews and Reports, 2019)

Neurotrophic Factors Mediated Activation of Astrocytes Ameliorate Memory Loss by Amyloid Clearance after Transplantation of Lineage Negative Stem Cells - P. Bali; A. Banik; B. Nehru; Akshay Anand (Molecular Neurobiology, 2019)

Phlorotannins from Padina tetrastromatica: structural characterisation and functional studies - Divya Nair; Muralidharan Vanuopadath; Akshaya Balasubramanian; Akshay Iyer; Shankar Ganesh; Abhishek Nair Anil; Vijesh Vikraman; Prasanth Pillai; Chinchu Bose; Bipin Gopalakrishnan Nair; Jayashree Gopalakrishna Pai; Sudarslal Sadasivan Nair (Journal of Applied Phycology, 2019)

Greener assembling of MoO3 nanoparticles supported on gum arabic: cytotoxic effects and catalytic efficacy towards reduction of p-nitrophenol - Saranya Kothaplamoottil Sivan; Akshay K.K. Padinjareveetil; Vinod V. T. Padil; Rajendra Pilankatta; Bini George; Chandra Senan; Miroslav Černík; Rajender S. Varma (Clean Technologies and Environmental Policy, 2019)

Discovery and Utilization of EST-SSR Marker Resource for Genetic Diversity and Population Structure Analyses of a Subtropical Bamboo, Dendrocalamus hamiltonii - Abhishek Bhandawat; Vikas Sharma; Pradeep Singh; Romit Seth; Akshay Nag; Jagdeep Kaur; Ram Kumar Sharma (Biochemical Genetics, 2019)

Preparation and Comparison of Oral Bioavailability for Different Nano-formulations of Olaparib - Akshay D. Pathade; Nagavendra Kommineni; Upendra Bulbake; Mohit M. Thummar; Gananadhamu Samanthula; Wahid Khan (AAPS PharmSciTech, 2019)

Proteomic study of endothelial dysfunction in response to homocysteinylated albumin - Reema Banarjee; Akshay Sharma; Shakuntala Bai; Arati Deshmukh; Mahesh Kulkarni (Journal of Proteins and Proteomics, 2019)

BjuWRR1, a CC-NB-LRR gene identified in Brassica juncea, confers resistance to white rust caused by Albugo candida - Heena Arora; K. Lakshmi Padmaja; Kumar Paritosh; Nitika Mukhi; A. K. Tewari; Arundhati Mukhopadhyay; Vibha Gupta; Akshay K. Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2019)

The hills are alive with geckos! A radiation of a dozen species on sky islands across peninsular India (Squamata: Gekkonidae, Hemiphyllodactylus) with the description of three new species - Ishan Agarwal; Akshay Khandekar; Varad B. Giri; Uma Ramakrishnan; K. Praveen Karanth (Organisms Diversity & Evolution, 2019)

Nanoencapsulated methyl salicylate as a biorational alternative of synthetic antifungal and aflatoxin B1 suppressive agents - Anupam Kujur; Amrita Yadav; Akshay Kumar; Prem Pratap Singh; Bhanu Prakash (Environmental Science and Pollution Research, 2019)

Alpha lipoic acid attenuates the long-term effects of lead exposure in retinal ischemic injury mouse model - Shweta Modgil; Sridhar Bammidi; Avijit Banik; Vijay Lakshmi Sharma; Akshay Anand (Environmental Science and Pollution Research, 2019)

Scale Minimization in Sugar Industry Evaporators using Nanoporous Industrial Bio-solid Waste Bagasse Fly Ash - Rajeev Nath Tiwari; Choudhary Akshay Gandharv; Keya Dharamvir; Suresh Kumar; Gaurav Verma (Sugar Tech, 2019)

Environmental impact assessment of uranium exploration and development on indigenous land in Labrador (Canada): a community-driven initiative - Atanu Sarkar; Derek H. C. Wilton; Erica Fitzgerald; Abhishek Sharma; Abhinav Sharma; Akshay Jinka Sathya (Environmental Geochemistry and Health, 2019)

NO protect the wheat embryo from oxidative damage by triggering the biochemical defence network and amylolytic activity - Ranjeet R. Kumar; Mohd. Tasleem; Khushboo Singh; Sumedha Ahuja; Akshay Sakhare; Sudhir Kumar; Suneha Goswami; Sivdhar Singh; Gyanendra P. Singh; Viswanathan Chinnusamy; Shelly Praveen (Plant Physiology Reports, 2019)

Molecular Speciation of Mycobacterial Isolates from Raw Cow Milk Reveals Predominance of Mycobacterium chelonae - Esther Vise; Akshay Garg; Sandeep Ghatak; Amarjit Karam; Uttaran Bhattacharjee; Arnab Sen; Ingudam Shakuntala; Kekungu Puro; Rajkumari Sanjukta; Neeta Raj Sharma; Samir Das (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Metal-Induced Pulmonary Fibrosis - Nour Assad; Akshay Sood; Matthew J. Campen; Katherine E. Zychowski (Current Environmental Health Reports, 2018)

Free tryptophan residues inhibit quorum sensing of Pseudomonas aeruginosa: a potential approach to inhibit the development of microbial biofilm - Poulomi Chakraborty; Akshay Vishnu Daware; Monika Kumari; Ahana Chatterjee; Disha Bhattacharyya; Garbita Mitra; Yusuf Akhter; Surajit Bhattacharjee; Prosun Tribedi (Archives of Microbiology, 2018)

Morphometric Analysis and Deoxyribonucleic Acid Barcoding of New Grapevine Pest, Stromatium barbatum (Fabricius) (Coleoptera: Cerambycidae) in India - Rajendra S. Jadhav; Deependra S. Yadav; Amala Udaykumar; Indu S. Sawant; Shashikant B. Ghule; Akshay M. Bhosale (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Molecular characterization of a new begomovirus infecting Synedrella nodiflora in South India - Soumita Das; Akshay Hegde; P. V. Shivaprasad (Archives of Virology, 2018)

Pretreated animal and human waste as a substantial nutrient source for cultivation of microalgae for biodiesel production - Vinod Kumar; Akshay Kumar; Manisha Nanda (Environmental Science and Pollution Research, 2018)

Data-Driven Methods for Advancing Precision Oncology - Prema Nedungadi; Akshay Iyer; Georg Gutjahr; Jasmine Bhaskar; Asha B. Pillai (Current Pharmacology Reports, 2018)

Clinical outcomes associated with carbapenem resistant Klebsiella pneumoniae (CRKP) in abdominal solid organ transplant (SOT) recipients - Tiffany E. Bias; Gregory E. Malat; Dong H. Lee; Akshay Sharma; Alden M. Doyle (Infectious Diseases, 2018)

What signals do herbivore-induced plant volatiles provide conspecific herbivores? - Subhash Shivaramu; Pagadala Damodaram Kamala Jayanthi; Vivek Kempraj; Raghavendra Anjinappa; Bakthavatsalam Nandagopal; Akshay Kumar Chakravarty (Arthropod-Plant Interactions, 2017)

Exploring the heat-responsive chaperones and microsatellite markers associated with terminal heat stress tolerance in developing wheat - Ranjeet R. Kumar; Suneha Goswami; Mohammad Shamim; Kavita Dubey; Khushboo Singh; Shweta Singh; Yugal K. Kala; Ravi R.K. Niraj; Akshay Sakhrey; Gyanendra P. Singh; Monendra Grover; Bhupinder Singh; et al. (Functional & Integrative Genomics, 2017)

Nanoscale wide-band semiconductors for photocatalytic remediation of aquatic pollution - Biplab Sarkar; Akshay Vishnu Daware; Priya Gupta; Kishore Kumar Krishnani; Sunandan Baruah; Surajit Bhattacharjee (Environmental Science and Pollution Research, 2017)

Development and Characterization of SSR Markers to Study Genetic Diversity and Population Structure of Horsegram Germplasm (Macrotyloma uniflorum) - R. K. Chahota; Divya Shikha; Maneet Rana; Vikas Sharma; Akshay Nag; T. R. Sharma; J. C. Rana; Hideki Hirakawa; Sachiko Isobe (Plant Molecular Biology Reporter, 2017)

Cyclone Frame Prediction by Gaussian Mixture Modeling of the Three Penultimate Time-Lapse Frames - Seba Susan; Achin Saxena; Anuvart Budhwar; Akshay Takhi; Abhishek Varshney (Journal of the Indian Society of Remote Sensing, 2017)

A preliminary application of dental cementum incremental analysis to determine the season-of-death of equids from the Xujiayao site, China - JingShu Li; ShuangQuan Zhang; Henry T. Bunn; Akshay Sarathi; Xing Gao (Science China Earth Sciences, 2017)

Transplantation of lineage-negative stem cells in pterygopalatine artery ligation induced retinal ischemia–reperfusion injury in mice - Gillipsie Minhas; Sudesh Prabhakar; Ryuichi Morishita; Munehisa Shimamura; Reema Bansal; Akshay Anand (Molecular and Cellular Biochemistry, 2017)

Genetic dissection of seed weight by QTL analysis and detection of allelic variation in Indian and east European gene pool lines of Brassica juncea - Namrata Dhaka; Kadambini Rout; Satish K. Yadava; Yaspal Singh Sodhi; Vibha Gupta; Deepak Pental; Akshay K. Pradhan (Theoretical and Applied Genetics, 2017)

Genetic Diversity and Structure of Pea (Pisum sativum L.) Germplasm Based on Morphological and SSR Markers - Jai C Rana; Maneet Rana; Vikas Sharma; Akshay Nag; Rakesh K Chahota; Tilak R Sharma (Plant Molecular Biology Reporter, 2017)

An investigation of reduced western disturbance activity over Northwest India in November - December 2015 compared to 2014 - A case study - Soumik Basu; Peter A. Bieniek; Akshay Deoras (Asia-Pacific Journal of Atmospheric Sciences, 2017)

Identification of genic SSRs and construction of a SSR-based linkage map in Brassica juncea - Namrata Dhaka; Arundhati Mukhopadhyay; Kumar Paritosh; Vibha Gupta; Deepak Pental; Akshay K. Pradhan (Euphytica, 2017)

Identification and characterization of novel UniGene-derived microsatellite markers in Podophyllum hexandrum (Berberidaceae) - AKSHAY NAG; PANKAJ BHARDWAJ; PARAMVIR SINGH AHUJA; RAM KUMAR SHARMA (Journal of Genetics, 2016)

A population approach to characterise amisulpride pharmacokinetics in older people and Alzheimer’s disease - Suzanne Reeves; Julie Bertrand; Fabrizia D’Antonio; Emma McLachlan; Akshay Nair; Stuart Brownings; Suki Greaves; Alan Smith; David Taylor; Robert Howard (Psychopharmacology, 2016)

First report of association of potato virus X and potato virus Y and ‘Candidatus Phytoplasma trifolii’ in brinjal in India - Manish Kumar; Akshay Katiyar; Madhupriya; G. P. Rao (VirusDisease, 2016)

Ex situ conservation of the endangered species Androcalva perlaria (Malvaceae) by micropropagation and cryopreservation - Susan E. Whiteley; Eric Bunn; Akshay Menon; Ricardo L. Mancera; Shane R. Turner (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Assessment of genetic diversity of Saltol QTL among the rice (Oryza sativa L.) genotypes - Showkat Ahmad Ganie; Mrinmoi Jyoti Borgohain; Kashyap Kritika; Akshay Talukdar; Dipti Ranjan Pani; Tapan Kumar Mondal (Physiology and Molecular Biology of Plants, 2016)

Novel microsatellite markers identification and diversity characterization in Pteris cretica L. - Vishal Kumar; Abhishek Bhandawat; Himanshu Sharma; Akshay Nag; Ram Kumar Sharma (Journal of Plant Biochemistry and Biotechnology, 2016)

Genetic diversity and population structure of endangered Aquilaria malaccensis revealed potential for future conservation - PRADEEP SINGH; AKSHAY NAG; RAJNI PARMAR; SNEHA GHOSH; BRIJMOHAN SINGH BHAU; RAM KUMAR SHARMA (Journal of Genetics, 2015)

Functionally relevant novel microsatellite markers for efficient genotyping in Stevia rebaudiana Bertoni - ABHISHEK BHANDAWAT; HIMANSHU SHARMA; AKSHAY NAG; SANATSUJAT SINGH; PARAMVIR SINGH AHUJA; RAM KUMAR SHARMA (Journal of Genetics, 2015)

Effective restoration of male-sterile (barnase) lines requires overlapping and higher levels of barstar expression: A multi-generation field analysis in Brassica juncea - Naveen C. Bisht; Arun Jagannath; Rehna Augustine; Pradeep K. Burma; Vibha Gupta; Akshay K. Pradhan; Deepak Pental (Journal of Plant Biochemistry and Biotechnology, 2015)

Production of Recombinant Human Granulocyte-Colony Stimulating Factor in Escherichia coli Using Novel Media Supplements Through Integrated Statistical Optimization Designs - Sandeep Vemula; Akshay Dedaniya; Rahul Bandaru; Maheswara Reddy Mallu; Vijaya Saradhi Settaluri; Srinivasa Reddy Ronda (International Journal of Peptide Research and Therapeutics, 2015)

A snapshot of microbial communities from the Kutch: one of the largest salt deserts in the World - Aanal S. Pandit; Madhvi N. Joshi; Poonam Bhargava; Inayatullah Shaikh; Garima N. Ayachit; Sandeep R. Raj; Akshay K. Saxena; Snehal B. Bagatharia (Extremophiles, 2015)

Geospatial and hydrological modeling to assess hydropower potential zones and site location over rainfall dependent Inland catchment - Manish Kumar Goyal; Vishal Singh; Akshay H. Meena (Water Resources Management, 2015)

Deciphering allelic variations for seed glucosinolate traits in oilseed mustard (Brassica juncea) using two bi-parental mapping populations - Kadambini Rout; Manisha Sharma; Vibha Gupta; Arundhati Mukhopadhyay; Yaspal S. Sodhi; Deepak Pental; Akshay K. Pradhan (Theoretical and Applied Genetics, 2015)

Erratum to: Genomic origin, expression differentiation and regulation of multiple genes encoding CYP83A1, a key enzyme for core glucosinolate biosynthesis, from the allotetraploid Brassica juncea - Meenu; Rehna Augustine; Manoj Majee; Akshay K. Pradhan; Naveen C. Bisht (Planta, 2015)

Genomic origin, expression differentiation and regulation of multiple genes encoding CYP83A1, a key enzyme for core glucosinolate biosynthesis, from the allotetraploid Brassica juncea - Meenu; Rehna Augustine; Manoj Majee; Akshay K. Pradhan; Naveen C. Bisht (Planta, 2015)

Development and characterization of polymorphic microsatellites markers in endangered Aquilaria malaccensis - Pradeep Singh; Himanshu Sharma; Akshay Nag; Brijmohan Singh Bhau; Ram Kumar Sharma (Conservation Genetics Resources, 2015)

Mapping of yellow mosaic virus (YMV) resistance in soybean (Glycine max L. Merr.) through association mapping approach - Bhupender Kumar; Akshay Talukdar; Khushbu Verma; Indu Bala; G. D. Harish; Sarmrat Gowda; S. K. Lal; R. L. Sapra; K. P. Singh (Genetica, 2015)

Population structure and association mapping studies for important agronomic traits in soybean - BHUPENDER KUMAR; AKSHAY TALUKDAR; INDU BALA; KHUSHBU VERMA; SANJAY KUMAR LAL; RAMESH LAL SAPRA; B. NAMITA; SUBHASH CHANDER; RESHU TIWARI (Journal of Genetics, 2014)

Tetralocular ovary and high silique width in yellow sarson lines of Brassica rapa (subspecies trilocularis) are due to a mutation in Bra034340 gene, a homologue of CLAVATA3 in Arabidopsis - Satish Kumar Yadava; Kumar Paritosh; Priya Panjabi-Massand; Vibha Gupta; Atika Chandra; Y. S. Sodhi; Akshay K. Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2014)

Cold-induced changes affect survival after exposure to vitrification solution during cryopreservation in the south-west Australian Mediterranean climate species Lomandra sonderi (Asparagaceae) - Akshay Menon; Bryn Funnekotter; Anja Kaczmarczyk; Eric Bunn; Shane Turner; Ricardo L. Mancera (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Role of iron in ischemia-induced neurodegeneration: mechanisms and insights - Gillipsie Minhas; Shweta Modgil; Akshay Anand (Metabolic Brain Disease, 2014)

Does toll-like receptor-3 (TLR-3) have any role in Indian AMD phenotype? - Neel Kamal Sharma; Kaushal Sharma; Amod Gupta; Sudesh Prabhakar; Ramandeep Singh; Pawan Kumar Gupta; Akshay Anand (Molecular and Cellular Biochemistry, 2014)

Metagenomics of petroleum muck: revealing microbial diversity and depicting microbial syntrophy - Madhvi N. Joshi; Shivangi V. Dhebar; Shivani V. Dhebar; Poonam Bhargava; Aanal Pandit; Riddhi P. Patel; Akshay Saxena; Snehal B. Bagatharia (Archives of Microbiology, 2014)

Development of an in vitro protocol for a difficult-to-propagate endemic Australian dryland sedge species Mesomelaena pseudostygia (Cyperaceae) - Simin Lai; Akshay Menon; Shane Turner; Andrea Kodym; Eric Bunn (In Vitro Cellular & Developmental Biology - Plant, 2014)

Natural mutations in two homoeologous TT8 genes control yellow seed coat trait in allotetraploid Brassica juncea (AABB) - Lakshmi K. Padmaja; Parul Agarwal; Vibha Gupta; Arundhati Mukhopadhyay; Yaspal S. Sodhi; Deepak Pental; Akshay K. Pradhan (Theoretical and Applied Genetics, 2014)

Soft computing and GIS for landslide susceptibility assessment in Tawaghat area, Kumaon Himalaya, India - D. Ramakrishnan; T. N. Singh; A. K. Verma; Akshay Gulati; K. C. Tiwari (Natural Hazards, 2013)

AFLP and RAPD based genetic diversity assessment of industrially important reed bamboo (Ochlandra travancorica Benth) - Akshay Nag; Priyanka Gupta; Vikas Sharma; Anil Sood; Paramvir Singh Ahuja; Ram Kumar Sharma (Journal of Plant Biochemistry and Biotechnology, 2013)

QTL mapping of yield-associated traits in Brassica juncea: meta-analysis and epistatic interactions using two different crosses between east European and Indian gene pool lines - Satish Kumar Yadava; N. Arumugam; Arundhati Mukhopadhyay; Yashpal Singh Sodhi; Vibha Gupta; Deepak Pental; Akshay K. Pradhan (Theoretical and Applied Genetics, 2012)

Computational Fluid Dynamics of Developing Avian Outflow Tract Heart Valves - Koonal N. Bharadwaj; Cassie Spitz; Akshay Shekhar; Huseyin C. Yalcin; Jonathan T. Butcher (Annals of Biomedical Engineering, 2012)

The emerging role of stem cells in ocular neurodegeneration: hype or hope? - Neeru Jindal; Asok Mukhopadhyay; Akshay Anand (Molecular and Cellular Biochemistry, 2012)

A CFD-based wind solver for an urban fast response transport and dispersion model - Akshay A. Gowardhan; Eric R. Pardyjak; Inanc Senocak; Michael J. Brown (Environmental Fluid Mechanics, 2011)

Genetic Structure of Indian Valerian (Valeriana jatamansi) Populations in Western Himalaya Revealed by AFLP - Subramani Rajkumar; Sunil Kumar Singh; Akshay Nag; Paramvir S. Ahuja (Biochemical Genetics, 2011)

Chromosome identification and karyotype analysis of Podophyllum hexandrum Roxb. ex Kunth using FISH - Akshay Nag; Subramani Rajkumar (Physiology and Molecular Biology of Plants, 2011)

Eliminating expression of erucic acid-encoding loci allows the identification of “hidden” QTL contributing to oil quality fractions and oil content in Brassica juncea (Indian mustard) - Arun Jagannath; Yashpal Singh Sodhi; Vibha Gupta; Arundhati Mukhopadhyay; Neelakantan Arumugam; Indira Singh; Soma Rohatgi; Pradeep Kumar Burma; Akshay Kumar Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2011)

Inhibition of Endogenous Hedgehog Signaling Protects Against Acute Liver Injury After Ischemia Reperfusion - Akshay Pratap; Ravikiran Panakanti; Ningning Yang; James D. Eason; Ram I. Mahato (Pharmaceutical Research, 2010)

Molecular mapping reveals two independent loci conferring resistance to Albugo candida in the east European germplasm of oilseed mustard Brassica juncea - Priya Panjabi-Massand; Satish Kumar Yadava; Pankaj Sharma; Arvinder Kaur; Amarendra Kumar; N. Arumugam; Yashpal Singh Sodhi; Arundhati Mukhopadhyay; Vibha Gupta; Akshay K. Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2010)

Evaluation of a fast response pressure solver for flow around an isolated cube - Akshay A. Gowardhan; Michael J. Brown; Eric R. Pardyjak (Environmental Fluid Mechanics, 2010)

Design, synthesis, and docking studies of telmisartan analogs for the treatment of metabolic syndrome - Cassia S. Mizuno; Amar G. Chittiboyina; Akshay Patny; Theodore W. Kurtz; Harrihar A. Pershadsingh; Robert C. Speth; Vardan T. Karamyan; Mitchell A. Avery (Medicinal Chemistry Research, 2009)

Design, synthesis, and docking studies of novel telmisartan–glitazone hybrid analogs for the treatment of metabolic syndrome - Amar G. Chittiboyina; Cassia S. Mizuno; Prashant V. Desai; Akshay Patny; Theodore W. Kurtz; Harrihar A. Pershadsingh; Robert C. Speth; Vardan Karamyan; Mitchell A. Avery (Medicinal Chemistry Research, 2009)

Artificial neural network and liquefaction susceptibility assessment: a case study using the 2001 Bhuj earthquake data, Gujarat, India - D. Ramakrishnan; T. N. Singh; N. Purwar; K. S. Barde; Akshay. Gulati; S. Gupta (Computational Geosciences, 2008)

Bacopa monniera exerts antiamnesic effect on diazepam-induced anterograde amnesia in mice - Sudesh Prabhakar; Manish Kumar Saraf; Promila Pandhi; Akshay Anand (Psychopharmacology, 2008)

A passage through in vitro culture leads to efficient production of marker-free transgenic plants in Brassica juncea using the Cre–loxP system - N. Arumugam; Vibha Gupta; Arun Jagannath; Arundhati Mukhopadhyay; Akshay K. Pradhan; Pradeep Kumar Burma; Deepak Pental (Transgenic Research, 2007)

Construction and characterization of 3-S Lines, an alternative population for mapping studies in rice (Oryza sativa L.) - Akshay Talukdar; Guiquan Zhang (Euphytica, 2007)

Retransformation of a male sterile barnase line with the barstar gene as an efficient alternative method to identify male sterile–restorer combinations for heterosis breeding - Naveen C. Bisht; Arun Jagannath; Pradeep K. Burma; Akshay K. Pradhan; Deepak Pental (Plant Cell Reports, 2007)

Forecasting shield pressures at a longwall face using artificial neural networks - Debasis Deb; Akshay Kumar; Rajat Pal Singh Rosha (Geotechnical and Geological Engineering, 2006)

Effect of herbal polyphenols on atherogenic transcriptome - Deepak Kaul; Akshay R. Shukla; Kavleen Sikand; Veena Dhawan (Molecular and Cellular Biochemistry, 2005)

The Effect of Wettability on Three-Phase Relative Permeability - David A. Dicarlo; Akshay Sahni; Martin J. Blunt (Transport in Porous Media, 2000)

Isolation of useful variants in alloplasmic crop brassicas in the cytoplasmic background of Erucastrum gallicum - Gadde U. Rao; Akshay K. Pradhan; Kundaranahalli R. Shivanna (Euphytica, 1998)

Absorption of Propranolol in Humans Following Oral, Jejunal, and Heal Administration - Akshay Buch; William H. Barr (Pharmaceutical Research, 1998)